Manufacturing method for semiconductor devices

JP2026165995APending Publication Date: 2026-10-14LINTEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058680
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、凹凸を有する半導体ウエハ等の部材であっても、ディンプルの発生を抑制しつつ、研削後の半導体ウエハ等の部材のTTVを良好に保って研削することが可能な、半導体装置の製造方法を提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165995000001_ABST
    Figure 2026165995000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a semiconductor device that can grind semiconductor wafers and other materials having an uneven surface while suppressing the generation of dimples and maintaining a good TTV after grinding. [Solution] The present invention relates to a method for manufacturing a semiconductor device, which uses a member having a circuit forming surface (α) and having irregularities on the circuit forming surface (α), and comprises the steps of: (S1) attaching a heat-fluid curable resin film to the circuit forming surface (α) to form a heat-fluid curable resin layer; (S2) curing the heat-fluid curable resin layer to form a cured resin film; (S3) attaching a backgrind sheet to the side of the cured resin film opposite to the circuit forming surface (α); and (S4) grinding the side of the member opposite to the circuit forming surface (α).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for manufacturing a semiconductor device. [Background technology]

[0002] In recent years, with the miniaturization and thinning of electronic devices, there has been an increasing demand for thinner and smaller semiconductor packages. Therefore, in the manufacturing of semiconductor devices, a process called backgrinding (grinding the back surface of semiconductor wafers and other materials) is commonly performed. In the case of semiconductor wafers, the backgrinding process is carried out by attaching an adhesive sheet (backgrinding sheet) to the circuit formation surface and protecting the circuit formation surface with the sheet (see, for example, Patent Document 1). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2000-328023 [Overview of the project] [Problems that the invention aims to solve]

[0004] In this case, the circuit formation surface of a semiconductor wafer may have irregularities formed by protruding electrodes, etc. When a backgrinding process is performed on such a circuit formation surface, problems may occur such as the formation of irregularities on the back side of the semiconductor wafer, i.e., the occurrence of dimples, or a deterioration in the thickness accuracy (TTV: total thickness variation) of the semiconductor wafer after grinding. Therefore, there was a need for a method of grinding semiconductor wafers and other materials that have irregularities, while suppressing the generation of dimples and maintaining a good TTV of the material after grinding.

[0005] The present invention aims to provide a method for manufacturing a semiconductor device that can grind semiconductor wafers and other materials having an uneven surface while suppressing the generation of dimples and maintaining a good TTV after grinding. [Means for solving the problem]

[0006] According to the present invention, the following [1] to

[12] are provided. [1] A method for manufacturing a semiconductor device using a member having a circuit forming surface (α) and having irregularities on the circuit forming surface (α), Step (S1) involves attaching a heat-fluidable curable resin film (x) to the circuit-forming surface (α) to form a heat-fluidable curable resin layer. The process of curing the aforementioned heat-fluidable curable resin layer to form a cured resin film (S2), Step (S3) involves attaching a backgrind sheet to the side of the cured resin film opposite to the circuit-forming surface (α), A method for manufacturing a semiconductor device, comprising the step (S4) of grinding the surface of the member opposite to the circuit forming surface (α). [2] The method for manufacturing a semiconductor device according to [1], wherein the complex viscosity of the heat-fluid curable resin film at 80°C is 15,000 Pa·s or less. [3] Furthermore, the method for manufacturing a semiconductor device according to [2], wherein the complex viscosity of the heat-fluidable curable resin film (x) at 130°C is 50 Pa·s or more. [4] A method for manufacturing a semiconductor device according to any one of [1] to [3], wherein the aforementioned thermofluid-curable resin film is further thermosetting. [5] A method for manufacturing a semiconductor device according to any one of [1] to [3], wherein the heat-fluidable curable resin film is further energy-ray curable. [6] The method for manufacturing a semiconductor device according to any one of [1] to [5], wherein the thermally fluid curable resin film (x) is a thermally fluid curable resin film composite sheet further having a support sheet. [7] The method for manufacturing a semiconductor device according to any one of [1] to [6], wherein the member is a member having protruding electrodes on the circuit formation surface (α). [8] The method for manufacturing a semiconductor device according to [7], wherein the height of the protruding electrode is 200 μm or less. [9] The method for manufacturing a semiconductor device according to [7] or [8], comprising a step (S5) of exposing the top of the protruding electrode after the step (S4).

[10] A thermally fluid curable resin film for use in the method for manufacturing a semiconductor device according to any one of [1] to [9].

[11] The thermally fluid curable resin film according to

[10] , which is thermally curable.

[12] The thermally fluid curable resin film according to

[10] , which is energy ray curable. [Advantageous Effects of the Invention]

[0007] According to the present invention, it is possible to provide a method for manufacturing a semiconductor device that can perform grinding while keeping the TTV of a member such as a ground semiconductor wafer favorable, suppressing the occurrence of dimples even for a member such as a semiconductor wafer having irregularities. [Brief Description of the Drawings]

[0008] [Figure 1] It is a schematic cross-sectional view showing an example of an embodiment of the composite sheet of the present embodiment. [Figure 2] It is a schematic cross-sectional view showing another example of the embodiment of the composite sheet of the present embodiment. [Figure 3] It is a schematic cross-sectional view showing still another example of the embodiment of the composite sheet of the present embodiment. [Figure 4]This is a schematic cross-sectional view showing an example of the embodiment of the back grind sheet of the present embodiment. [Figure 5] This is a schematic cross-sectional view showing another example of the embodiment of the back grind sheet of the present embodiment. [Figure 6] This is a schematic cross-sectional view showing an example of step (S11) in step (S1). [Figure 7] This is a schematic cross-sectional view showing an example of step (S12) in step (S1). [Figure 8] This is a schematic cross-sectional view showing an example of step (S2). [Figure 9] This is a schematic cross-sectional view showing an example of step (S3). [Figure 10] This is a schematic cross-sectional view showing an example of step (S4). [Figure 11] This is a schematic cross-sectional view showing an example of step (S6). [Figure 12] This is a schematic cross-sectional view showing another example of step (S6). [Modes for Carrying Out the Invention]

[0009] In the present specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values in terms of standard polystyrene measured by a gel permeation chromatography (GPC) method, and specifically are values measured based on the methods described in the Examples.

[0010] In the present specification, for preferred numerical ranges (for example, ranges such as content), the lower limit values and upper limit values described stepwise can be independently combined. For example, from the description "preferably 10 to 90, more preferably 30 to 60", the "preferred lower limit value (10)" and the "more preferred upper limit value (60)" can be combined to form "10 to 60".

[0011] In this specification, "energy beam" means an electromagnetic wave or charged particle beam that has an energy quantum. Examples of energy beams include ultraviolet rays, radiation, and electron beams. Ultraviolet rays can be irradiated using electrodeless lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, black lights, LED lamps, etc. Electron beams can be irradiated using those generated by electron accelerators, etc.

[0012] In this specification, "energy ray curable" means the property of hardening by irradiation with energy rays. Also in this specification, "thermosetting" means the property of hardening by heating, and "non-curable" means the property of not hardening by heating or irradiation with energy rays.

[0013] In this specification, for example, "(meth)acrylic acid" refers to both "acrylic acid" and "methacrylic acid," and the same applies to other similar terms.

[0014] In this specification, "protruding electrode" refers to a protruding electrode of a shape commonly used on the circuit formation surface of semiconductor wafers, semiconductor chips, etc., such as ball bumps and pillar electrodes.

[0015] In this specification, the "thickness" of an object means the total thickness of the object as a whole. For example, if the object consists of multiple layers, it means the total thickness of all the layers that make up the object. In this specification, unless otherwise specified, the "thickness" of an object refers to the average value of the thickness measured at five randomly selected locations on the object, and can be obtained using a constant-pressure thickness measuring instrument in accordance with JIS K 7130:1999.

[0016] In this specification, "solid content" or "active ingredient" refers to the components of the composition in question, excluding diluting solvents such as water and organic solvents.

[0017] The mechanism of action described herein is speculative and does not limit the mechanism by which the present invention achieves its effects.

[0018] In order to make the features of the present invention easier to understand, the drawings may show enlarged versions of key parts for convenience, and the dimensional ratios of each component may not be the same as in reality.

[0019] [Method for manufacturing the semiconductor device of this embodiment] The semiconductor device manufacturing method of this embodiment is a method for manufacturing a semiconductor device using a member having a circuit forming surface (α) and having irregularities on the circuit forming surface (α), Step (S1) involves attaching a heat-fluidable curable resin film (x) to the circuit-forming surface (α) to form a heat-fluidable curable resin layer. The process of curing the aforementioned heat-fluidable curable resin layer to form a cured resin film (S2), Step (S3) involves attaching a backgrind sheet to the side of the cured resin film opposite to the circuit-forming surface (α), A method for manufacturing a semiconductor device, comprising the step (S4) of grinding the surface of the member opposite to the circuit forming surface (α).

[0020] As mentioned above, for example, the circuit formation surface of a semiconductor wafer may have irregularities formed by protruding electrodes, etc. If the backgrind sheet does not adequately absorb the irregularities of the semiconductor wafer on such a circuit formation surface, irregularities may form on the surface of the backgrind sheet. If the semiconductor wafer is ground in this state, the problem of dimple formation may occur. The inventors of the present invention conducted diligent research to solve the above problems. As a result, they found that the above problems can be solved by forming a cured resin film on the circuit-forming surface (α) of the member having irregularities, and then applying a backgrind sheet and performing a backgrinding process. One possible reason for this is the following mechanism: Specifically, a heat-fluidable curable resin film (x) is first applied to the circuit-forming surface (α) of the component, which has irregularities, thereby forming a heat-fluidable curable resin layer. Subsequently, a cured resin film is formed by a curing process. In the initial stages of cured resin film formation, the heat-fluidable curable resin layer becomes fluid, so even if irregularities occur in the heat-fluidable curable resin layer due to the irregularities of the component, its surface becomes flat. As a result, the occurrence of irregularities caused by the irregularities of the component is suppressed, and the irregularities that cause dimples and TTV become flat. Therefore, it is considered that the TTV of components such as semiconductor wafers after grinding can be maintained well while suppressing the occurrence of dimples during the back-grinding process. Furthermore, when a backgrind sheet is directly attached to a circuit-forming surface (α) of a component that has irregularities, adhesive residue may be generated when peeling off the backgrind sheet, especially near the base of the protrusions. However, in this embodiment, the irregularities are embedded in a cured resin film, and the backgrind sheet is attached on top of it, thus suppressing the generation of adhesive residue. Furthermore, when a backgrind sheet is directly attached to a circuit-forming surface (α) having irregularities on the component, depending on the thickness of the backgrind sheet, air bubbles may become trapped between the adhesive layer and the circuit-forming surface, which can lead to the formation of dimples and deterioration of TTV. However, in this embodiment, the irregularities are embedded in the cured resin film, and the backgrind sheet is attached on top of it, thus suppressing the trapping of air bubbles.

[0021] In this embodiment, the member having the circuit formation surface (α) is not particularly limited, but an example is a semiconductor wafer. When the member having the circuit formation surface (α) is a semiconductor wafer, for example, electrodes, wiring, and elements such as transistors formed on the surface of the semiconductor wafer form irregularities, but it is preferable that protruding electrodes are formed. That is, it is preferable that the member having irregularities is a member equipped with protruding electrodes. Furthermore, in the semiconductor chip manufacturing process, even if irregularities are unexpectedly formed on the surface of the semiconductor wafer due to fine particles such as dust and dirt adhering to the surface; minute deformation due to stress; minute unevenness due to uneven reactions during etching and cleaning; minute scratches formed during transportation, etc., it is expected that the generation of dimples can be suppressed while maintaining good TTV of the semiconductor wafer and other components after grinding.

[0022] In this specification, the irregularities formed on the circuit-forming surface (α) of the component can be observed by known methods, such as observing the surface of the component with a microscope such as an optical microscope or a scanning electron microscope, or using an optical interference non-contact surface shape measuring instrument such as VertScan (manufactured by Ryoka Systems Co., Ltd.). Furthermore, in this specification, "height of the protrusion" means the distance in the thickness direction of the member between the highest point of the protrusion relative to the circuit forming surface and the circuit forming surface, and "depth of the recess" means the distance in the thickness direction of the member between the lowest point of the recess relative to the circuit forming surface and the circuit forming surface. The aforementioned "height of the protrusions" and "depth of the recesses" can be measured by known methods. For example, this can be done by cutting the part of the material with irregularities along the thickness direction of the material and observing the cross-section with a microscope such as an optical microscope or a scanning electron microscope, or by using an optical interference non-contact surface shape measuring instrument such as VertScan (manufactured by Ryoka Systems Co., Ltd.).

[0023] In this embodiment, the height of the protrusions that form the irregularities on the circuit-forming surface (α) of the member is preferably 5 to 200 μm, more preferably 10 to 100 μm, and even more preferably 20 to 50 μm. The same applies when the aforementioned protrusion is a protruding electrode, in which case the height of the protruding electrode is preferably 5 to 200 μm, more preferably 10 to 100 μm, and even more preferably 20 to 50 μm.

[0024] Hereinafter, the thermofluid-curable resin film (x) used in the semiconductor device manufacturing method described above, and the thermofluid-curable resin film composite sheet including the thermofluid-curable resin film (x) and support sheet will be described in detail, followed by a detailed explanation of each step.

[0025] <Thermo-fluid curable resin film (x)> The heat-fluidable curable resin film (x) is used in step (S1) to form a heat-fluidable curable resin layer on the circuit-forming surface (α) of the component which has irregularities. As mentioned above, by embedding the circuit-forming surface (α) with irregularities in the component into the cured resin film before the backgrinding process, the influence of irregularities that cause dimples and TTVs can be reduced.

[0026] In this embodiment, "thermofluidly curable resin film" refers to a film that maintains its shape at room temperature (5°C to 35°C), becomes fluid when heated to a temperature T higher than room temperature (60°C to 100°C), and hardens when "(1) heated to a temperature even higher than temperature T" or "(2) irradiated with energy rays," thereby becoming a cured resin film. In the phrase "(1) Heating at a temperature higher than temperature T", "(1) A temperature higher than temperature T" specifically means that "90°C to 200°C" is preferred, "110°C to 170°C" is more preferred, and "120°C to 140°C" is even more preferred.

[0027] The heat-fluidable curable resin film (x) may consist of only one layer or two or more layers. If the heat-fluidable curable resin film (x) consists of multiple layers, these layers may be identical or different from each other, and the combination of these layers is not particularly limited.

[0028] The thickness of the heat-fluidable curable resin film (x) is adjusted as appropriate, taking into consideration the thickness of the cured resin film formed by curing the heat-fluidable curable resin film (x), the surface irregularities of the component, etc. The thickness of the heat-fluidable curable resin film (x) is preferably 5 to 70 μm, more preferably 10 to 60 μm, and even more preferably 15 to 50 μm. When the thickness of the heat-fluidable curable resin film (x) is greater than or equal to the lower limit, it is easier to produce a film with high in-plane uniformity. Conversely, when the thickness of the heat-fluidable curable resin film (x) is less than or equal to the upper limit, it is prevented from becoming excessively thick. Furthermore, from the viewpoint of making it easier to flatten the irregularities on the surface of the member, the thickness of the heat-fluidable curable resin film (x) is preferably 10 to 20 μm thicker than the height of the protrusions on the surface of the member. For example, when the height of the protrusions is 40 μm, the thickness of the heat-fluidable curable resin film (x) is preferably 40 to 70 μm, more preferably 45 to 65 μm, and even more preferably 50 to 60 μm.

[0029] Here, the thickness T [μm] of the heat-fluidable curable resin film (x) may be calculated using the following formula. T = H × (100 - Vb) / 100 × (2 + C) In the above formula, H is the height of the protrusion [μm], Vb is the percentage [%] of the space occupied by the protrusion in the circuit-forming surface (α) of the member, between the circuit-forming surface (α) and the surface formed by connecting the vertices of the protrusions, and C is any number in the range of 0 to 0.10.

[0030] (Complex viscosity of the thermofluid-curable resin film (x)) The upper limit of the complex viscosity of the thermofluid-curable resin film (x) at 80°C in this embodiment is preferably 15,000 Pa·s or less, more preferably 13,500 Pa·s or less, even more preferably 12,000 Pa·s or less, even more preferably 10,500 Pa·s or less, and still still preferably 10,000 Pa·s or less, from the viewpoint of improving the embedding ability of the thermofluid-curable resin film (x) into the irregularities on the circuit-forming surface (α) of the member and facilitating the flattening of the surface of the thermofluid-curable resin layer. Furthermore, the lower limit of the complex viscosity at 80°C is preferably 100 Pa·s or higher, more preferably 200 Pa·s or higher, even more preferably 300 Pa·s or higher, even more preferably 400 Pa·s or higher, and still more preferably 500 Pa·s or higher, from the viewpoint of suppressing excessive fluidity. In other words, the thermofluid curable resin film (x) of this embodiment has a complex viscosity at 80°C that is preferably 100 to 15,000 Pa·s, more preferably 200 to 13,500 Pa·s, even more preferably 300 Pa·s to 12,000 Pa·s, even more preferably 400 to 10,500 Pa·s, and still more preferably 500 to 10,000 Pa·s.

[0031] Furthermore, from the viewpoint of making it easier to prevent the heat-fluid-curable resin film (x) from repelling when it is applied, the lower limit of the complex viscosity of the heat-fluid-curable resin film (x) at 130°C is preferably 50 Pa·s or more, more preferably 100 Pa·s or more, even more preferably 200 Pa·s or more, and even more preferably 400 Pa·s or more. Furthermore, from the viewpoint of facilitating processing such as cutting the head, the upper limit of the complex viscosity of the heat-fluidable curable resin film (x) at 130°C is preferably 25,000 Pa·s or less, more preferably 20,000 Pa·s or less, even more preferably 15,000 Pa·s or less, and even more preferably 12,000 Pa·s or less. In other words, the thermofluid curable resin film (x) of this embodiment has a complex viscosity at 130°C that is preferably 50 to 25,000 Pa·s, more preferably 100 to 20,000 Pa·s, even more preferably 200 Pa·s to 15,000 Pa·s, and even more preferably 400 to 12,000 Pa·s.

[0032] Furthermore, the complex viscosity of a thermofluidly curable resin film (x) can be easily adjusted by adjusting one or both of the types and contents of the components contained in the thermofluidly curable resin film (x). To do this, one or both of the types and contents of the components contained in the composition for forming the thermofluidly curable resin film (x) should be adjusted. For example, by adjusting one or both of the types and contents of the main components, such as polymer components (A) and fillers (D), and by adjusting one or both of the types and contents of one or more additives (G) selected from rheology control agents, surfactants, and silicone oils, the complex viscosity of the thermofluidly curable resin film (x) in dynamic viscoelasticity measurements can be easily adjusted. For example, increasing the content of one or both of the filler (D) and additive (G) in the thermofluid curable resin film (x) makes it easier to adjust the complex viscosity in the dynamic viscoelasticity measurement of the thermofluid curable resin film (x) to a larger value, and as a result, it becomes easier to adjust the complex viscosity to an appropriate value.

[0033] In this embodiment, the complex viscosity of the thermofluid-curable resin film (x) can be measured, for example, by dynamic viscoelasticity measurement as described below.

[0034] Multiple layers of heat-fluid curable resin film (x) are laminated to form a heat-fluid curable resin film layer with a thickness of 1 mm. A cylindrical evaluation sample with a diameter of 25 mm and a thickness of 1 mm is prepared from this heat-fluid curable resin film layer, and this sample is placed in a shear viscosity measuring device (Anton Paar "MCR301"). At this time, the sample is placed on the installation location of the measuring device, and the sample is fixed in place by pressing a measuring jig against the top surface of the sample. Under the following measurement conditions, the viscosity is measured at intervals from room temperature to 150°C, and the viscosity at 80°C and 130°C is determined. • Frequency: 11Hz • Heating rate: 10℃ / min • Applied strain: 0.1%

[0035] <Composition of the thermofluid-curable resin film (x)> The thermofluid-curable resin film (x) used in the semiconductor device manufacturing method of this embodiment may be thermosetting, which hardens by heating, or energy-ray curable, which hardens by energy ray irradiation. The following describes the "thermofluid thermosetting resin film (x1)" which hardens by heating and the "thermofluid energy ray curable resin film (x2)" which hardens by energy ray irradiation. In the following explanation, "thermofluid thermosetting resin film (x1)" may also be referred to as "thermosetting resin film (x1)". Furthermore, "thermofluid energy ray curable resin film (x2)" is sometimes referred to as "energy ray curable resin film (x2)".

[0036] (Composition of thermosetting resin film (x1)) The thermosetting resin film (x1) of this embodiment contains a polymer component (A) and a thermosetting component (B). The thermosetting resin film (x1) is formed, for example, from a thermosetting resin composition (x1-1) containing a polymer component (A) and a thermosetting component (B). Polymeric component (A) is a component that can be considered to have been formed by a polymerization reaction of polymerizable compounds. Thermosetting component (B) is a component that can undergo a curing (polymerization) reaction triggered by heat. This curing (polymerization) reaction includes polycondensation reactions.

[0037] (Polymer component (A)) The thermosetting resin film (x1) and thermosetting resin composition (x1-1) of this embodiment contain a polymer component (A). Polymer component (A) is a polymer compound used to impart film-forming properties, flexibility, and other characteristics to the thermosetting resin film (x1). Polymer component (A) may be used alone or in combination of two or more types. When two or more polymer components (A) are used in combination, the combination and ratio can be arbitrarily selected.

[0038] Examples of polymer components (A) include acrylic resins, polyarylate resins, acetal resins, polyesters, urethane resins (resins having urethane bonds), acrylic urethane resins, silicone resins (resins having siloxane bonds), rubber resins (resins having a rubber structure), phenoxy resins, and thermosetting polyimides. Among these, acrylic resins, polyarylate resins, and acetal resins are preferred, with acetal resins being more preferred.

[0039] Examples of acrylic resins include well-known acrylic polymers. The weight-average molecular weight (Mw) of the acrylic resin is preferably 10,000 to 2,000,000, more preferably 300,000 to 1,500,000, and even more preferably 500,000 to 1,000,000. Having a weight-average molecular weight of the acrylic resin above the lower limit mentioned above makes it easier to improve the dimensional stability (stable over time during storage) of the thermosetting resin film (x1). Furthermore, having a weight-average molecular weight of the acrylic resin below the upper limit mentioned above makes it easier for the thermosetting resin film (x1) to conform to the irregularities on the circuit-forming surface (α) of the component, for example, making it easier to suppress the generation of voids between the component and the thermosetting resin film (x1). Consequently, it is also easier to improve the embedding ability into the irregularities on the circuit-forming surface (α) of the component.

[0040] The glass transition temperature (Tg) of the acrylic resin is preferably -60 to 70°C, more preferably -40 to 50°C, and even more preferably -30 to 30°C, from the viewpoint of the adhesiveness and handling properties of the thermosetting resin film (x1).

[0041] Examples of acrylic resins include polymers of one or more (meth)acrylic acid esters; copolymers of two or more monomers selected from (meth)acrylic acid, itaconic acid, vinyl acetate, acrylonitrile, styrene, and N-methylolacrylamide, etc.

[0042] Examples of (meth)acrylic acid esters that constitute acrylic resins include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, and (meth) Alkyl methacrylates such as isononyl acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl ((meth)acrylate) (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl ((meth)acrylate) (myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl ((meth)acrylate) (palmityl (meth)acrylate), heptadecyl (meth)acrylate, and octadecyl ((meth)acrylate) (stearyl (meth)acrylate), in which the alkyl group constituting the alkyl ester has a chain structure with 1 to 18 carbon atoms; Cycloalkyl esters of (meth)acrylates, such as isobornyl (meth)acrylate and dicyclopentanyl (meth)acrylate; (meth)acrylate aralkyl esters such as benzyl (meth)acrylate; (meth)acrylate dicyclopentenyl ester and other cycloalkenyl (meth)acrylates; (meth)acrylate cycloalkenyloxyalkyl esters such as (meth)acrylate dicyclopentenyloxyethyl ester; (meth)acrylimide; Glycidyl group-containing (meth)acrylic acid esters such as glycidyl (meth)acrylate; Hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, and other hydroxyl group-containing (meth)acrylate esters; Examples include (meth)acrylic acid esters containing substituted amino groups, such as N-methylaminoethyl (meth)acrylate. In this specification, "substituted amino group" means a group in which one or two hydrogen atoms of an amino group are replaced by a group other than a hydrogen atom. Among these, from the viewpoint of film-forming properties of the thermosetting resin film (x1) and the adherence of the thermosetting resin film (x1) to the surface of the member, it is preferable that the alkyl group constituting the alkyl ester is a copolymer of (meth)acrylate alkyl ester having a chain structure with 1 to 18 carbon atoms, glycidyl group-containing (meth)acrylate ester, and hydroxyl group-containing (meth)acrylate ester; it is more preferable that the alkyl group constituting the alkyl ester is a copolymer of (meth)acrylate alkyl ester having a chain structure with 1 to 4 carbon atoms, glycidyl group-containing (meth)acrylate ester, and hydroxyl group-containing (meth)acrylate ester; and it is even more preferable that it is a copolymer of butyl acrylate, methyl acrylate, glycidyl acrylate, and 2-hydroxyethyl acrylate.

[0043] The acrylic resin may be obtained by copolymerizing one or more monomers selected from, for example, (meth)acrylic acid ester, (meth)acrylic acid, itaconic acid, vinyl acetate, acrylonitrile, styrene, and N-methylolacrylamide, in addition to (meth)acrylic acid ester.

[0044] The monomers that make up the acrylic resin may be used individually or in combination of two or more. When the monomers that make up the acrylic resin are two or more, their combination and ratio can be arbitrarily selected.

[0045] Examples of polyarylate resins in polymer component (A) include known resins, such as those whose basic structure is the polycondensation of a divalent phenol with a dibasic acid such as phthalic acid or a carboxylic acid. Among these, polycondensates of bisphenol A and phthalic acid, poly-4,4'-isopropylidenediphenylene terephthalate / isophthalate copolymers, and their derivatives are preferred.

[0046] Examples of the acetal resin in polymer component (A) include those that are well known. Among these, preferred acetal resins include, for example, polyvinyl formal and polyvinyl butyral, with polyvinyl butyral being the most preferred. Examples of polyvinyl butyral include those having constituent units represented by the following formulas (i)-1, (i)-2, and (i)-3.

[0047] [ka]

[0048] (In the formula, l, m, and n are each an independent integer greater than or equal to 1.)

[0049] The weight-average molecular weight (Mw) of the polyvinyl acetal resin (preferably polyvinyl butyral) is preferably 5,000 to 200,000, more preferably 8,000 to 100,000, even more preferably 8,000 to 50,000, and even more preferably 10,000 to 35,000. Having a weight-average molecular weight of the polyvinyl acetal resin (preferably polyvinyl butyral) above the lower limit of the above-mentioned values ​​makes it easier to improve the shape stability (stable over time during storage) of the thermosetting resin film (x1). Furthermore, having a weight-average molecular weight of the polyvinyl acetal resin (preferably polyvinyl butyral) below the upper limit of the above-mentioned values ​​makes it easier for the thermosetting resin film (x1) to conform to the uneven surface of the component, for example, making it easier to suppress the generation of voids between the component and the thermosetting resin film (x1). Therefore, it is also easier to improve the embedding ability into the irregularities on the circuit-forming surface (α) of the component.

[0050] The glass transition temperature (Tg) of polyvinyl acetal resin (preferably polyvinyl butyral) is preferably 40 to 80°C, and more preferably 50 to 70°C, from the viewpoint of film-forming properties of the thermosetting resin film (x1).

[0051] The ratio of three or more monomers that make up the polyvinyl acetal resin (preferably polyvinyl butyral) can be arbitrarily selected.

[0052] In the thermosetting resin film (x1) and the thermosetting resin composition (x1-1), the content of polymer component (A) is preferably 2 to 30% by mass, more preferably 3 to 25% by mass, and even more preferably 3 to 15% by mass, based on the total amount of active ingredients.

[0053] Polymer component (A) may also correspond to thermosetting component (B). In this embodiment, if the thermosetting resin film (x1) and thermosetting resin composition (x1-1) contain components that correspond to both polymer component (A) and thermosetting component (B), the thermosetting resin film (x1) and thermosetting resin composition (x1-1) are considered to contain both polymer component (A) and thermosetting component (B).

[0054] (Thermosetting component (B)) The thermosetting resin film (x1) and the thermosetting resin composition (x1-1) contain a thermosetting component (B). The thermosetting component (B) is a component that cures the thermosetting resin film (x1) to form a hard, cured resin film. The thermosetting component (B) may be used alone or in combination of two or more types. If there are two or more types of thermosetting component (B), their combination and ratio can be arbitrarily selected.

[0055] Examples of thermosetting component (B) include epoxy thermosetting resins, thermosetting polyimides, polyurethanes, unsaturated polyesters, and silicone resins. Among these, epoxy thermosetting resins are preferred. When thermosetting component (B) is an epoxy thermosetting resin, the protective properties of the cured resin film are enhanced, and warping of the cured resin film can be suppressed.

[0056] Epoxy thermosetting resins consist of an epoxy resin (B1) and a thermosetting agent (B2). Epoxy thermosetting resins may be used individually or in combination of two or more types. When two or more epoxy thermosetting resins are used, their combination and ratio can be arbitrarily selected.

[0057] -Epoxy resin (B1)- The epoxy resin (B1) is not particularly limited, but from the viewpoint of making it easier to exhibit the effects of the present invention, it is preferable to use a combination of an epoxy resin that is solid at room temperature (hereinafter also referred to as a solid epoxy resin) and an epoxy resin that is liquid at room temperature (hereinafter also referred to as a liquid epoxy resin). In this specification, "room temperature" refers to 5 to 35°C, preferably 15 to 25°C.

[0058] The liquid epoxy resin is not particularly limited as long as it is liquid at room temperature. Examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, glycidyl ester type epoxy resin, biphenyl type epoxy resin, and phenylene skeleton type epoxy resin. Among these, bisphenol A type epoxy resin is preferred. Liquid epoxy resin may be used alone or in combination of two or more types. When two or more types of liquid epoxy resin are used, their combination and ratio can be arbitrarily selected.

[0059] The epoxy equivalent of the liquid epoxy resin is preferably 200 to 600 g / eq, more preferably 250 to 550 g / eq, and even more preferably 300 to 500 g / eq. The epoxy equivalent in this embodiment can be measured in accordance with JIS K 7236:2009.

[0060] The solid epoxy resin is not particularly limited as long as it is solid at room temperature. Examples include biphenyl-type epoxy resin, bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, orthocresol novolac epoxy resin, dicyclopentadiene-type epoxy resin, naphthalene-type epoxy resin, anthracene-type epoxy resin, and fluorene-based epoxy resin. Among these, naphthalene-type epoxy resin, dicyclopentadiene-type epoxy resin, and fluorene-based epoxy resin are preferred, with dicyclopentadiene-type epoxy resin being more preferred. Solid epoxy resins may be used individually or in combination of two or more types. If two or more types of solid epoxy resins are used, their combination and ratio can be arbitrarily selected.

[0061] The epoxy equivalent of the solid epoxy resin is preferably 150 to 450 g / eq, and more preferably 150 to 400 g / eq.

[0062] The ratio of liquid epoxy resin (xe) to solid epoxy resin (ye) [(xe) / (ye)] is preferably 0.01 to 10.0 by mass, more preferably 0.02 to 8.0, and even more preferably 0.03 to 6.0. When the above ratio [(xe) / (ye)] is within the above range, it is possible to suppress the generation of cutting chips and the like when cutting the cured resin film with a dicing blade after curing, thereby improving machinability.

[0063] The number-average molecular weight of the epoxy resin (B1) is not particularly limited, but from the viewpoint of the curability of the thermosetting resin film (x1) and the strength and heat resistance of the cured resin film after curing, it is preferably 300 to 30,000, more preferably 400 to 10,000, and even more preferably 500 to 3,000.

[0064] -Thermosetting agent (B2)- The thermosetting agent (B2) functions as a curing agent for the epoxy resin (B1). Examples of the thermosetting agent (B2) include compounds having two or more functional groups capable of reacting with epoxy groups in one molecule. Examples of the above functional groups include phenolic hydroxyl groups, alcoholic hydroxyl groups, amino groups, carboxyl groups, and groups in which an acid group has been converted into an anhydride. It is preferable that the functional group is a phenolic hydroxyl group, an amino group, or a group in which an acid group has been converted into an anhydride, and it is more preferable that the functional group is a phenolic hydroxyl group or an amino group.

[0065] Examples of thermosetting agents (B2) that include phenolic curing agents having phenolic hydroxyl groups include polyfunctional phenolic resins, biphenols, novolac-type phenolic resins, dicyclopentadiene-based phenolic resins, and aralkylphenolic resins. Among the thermosetting agents (B2), examples of amine-based curing agents having an amino group include dicyandiamide (hereinafter sometimes abbreviated as "DICY"). Among these, phenolic curing agents having phenolic hydroxyl groups are preferred, and novolac-type phenolic resins are more preferred.

[0066] Among the thermosetting agents (B2), the number average molecular weight of the resin components, such as polyfunctional phenolic resins, novolac-type phenolic resins, dicyclopentadiene-based phenolic resins, and aralkylphenolic resins, is preferably 300 to 30,000, more preferably 400 to 10,000, and even more preferably 500 to 3,000. The molecular weight of the non-resin component of the thermosetting agent (B2), such as biphenol or dicyandiamide, is not particularly limited, but is preferably 60 to 500.

[0067] The thermosetting agent (B2) may be used alone or in combination of two or more types. If there are two or more types of thermosetting agent (B2), their combination and ratio can be arbitrarily selected.

[0068] In the thermosetting resin film (x1) and thermosetting resin composition (x1-1), the content of the thermosetting agent (B2) is preferably 0.010 to 200 parts by mass, more preferably 0.020 to 150 parts by mass, even more preferably 0.050 to 100 parts by mass, and even more preferably 0.10 to 77 parts by mass, based on the content of 100 parts by mass of the epoxy resin (B1). When the content of the thermosetting agent (B2) is above the lower limit, the curing of the thermosetting resin film (x1) proceeds more easily. Furthermore, when the content of the thermosetting agent (B2) is below the upper limit, the moisture absorption rate of the thermosetting resin film (x1) is reduced, and the reliability of semiconductor devices, etc., obtained using the thermosetting resin film (x1) is further improved.

[0069] In the thermosetting resin film (x1) and thermosetting resin composition (x1-1), the content of the thermosetting component (B) (total content of epoxy resin (B1) and thermosetting agent (B2)) is preferably 200 to 10,000 parts by mass, more preferably 300 to 5,000 parts by mass, and even more preferably 400 to 1,000 parts by mass, per 100 parts by mass of the polymer component (A), from the viewpoint of enhancing the protective properties of the cured resin film.

[0070] -Curing accelerator (C)- The thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may contain a curing accelerator (C). The curing accelerator (C) is an ingredient used to adjust the curing rate of the thermosetting resin film (x1). Preferred curing accelerators (C) include, for example, tertiary amines such as triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; imidazoles such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole (imidazoles in which one or more hydrogen atoms are substituted with groups other than hydrogen atoms); organophosphines such as tributylphosphine, diphenylphosphine, and triphenylphosphine (phosphines in which one or more hydrogen atoms are substituted with organic groups); and tetraphenylboron salts such as tetraphenylphosphonium tetraphenylborate and triphenylphosphine tetraphenylborate. Among these, imidazoles are preferred, and 2-phenyl-4,5-dihydroxymethylimidazole is more preferred, from the viewpoint of making it easier to exhibit the effects of the present invention.

[0071] The curing accelerator (C) may be used alone or in combination of two or more types. If there are two or more types of curing accelerator (C), their combination and ratio can be arbitrarily selected.

[0072] In the thermosetting resin film (x1) and thermosetting resin composition (x1-1), when a curing accelerator (C) is used, the content of the curing accelerator (C) is preferably 0.001 to 10 parts by mass, and more preferably 0.01 to 5 parts by mass, per 100 parts by mass of the content of the thermosetting component (B). When the content of the curing accelerator (C) is above the lower limit, the effects of using the curing accelerator (C) are more easily obtained. Furthermore, when the content of the curing accelerator (C) is below the upper limit, for example, the effect of suppressing the migration and segregation of highly polar curing accelerators (C) to the adhesive interface side with the component in the thermosetting resin film (x1) under high temperature and high humidity conditions is enhanced, and the reliability of semiconductor devices etc. obtained using the thermosetting resin film (x1) is further improved.

[0073] -Filling material (D)- The thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may contain a filler (D). By including a filler (D) and satisfying the above parameters, the chipping suppression of the cured resin film obtained by curing the thermosetting resin film (x1) can be easily improved. Furthermore, by including the filler (D), it becomes easier to adjust the coefficient of thermal expansion of the cured resin film obtained by curing the thermosetting resin film (x1) to an appropriate range, thereby further improving the reliability of semiconductor devices and the like obtained using the thermosetting resin film (x1). In addition, by including the filler (D) in the thermosetting resin film (x1), it is also possible to reduce the moisture absorption rate of the cured resin film and improve its heat dissipation.

[0074] The filler (D) may be either an organic filler or an inorganic filler, but it is preferably an inorganic filler or an organic / inorganic hybrid filler. Preferred inorganic fillers include, for example, powders such as silica, talc, calcium carbonate, and boron nitride; beads formed from these inorganic fillers in a spherical shape; surface modified products of these inorganic fillers; single crystal fibers of these inorganic fillers; and glass fibers. Preferred organic / inorganic hybrid fillers include, for example, component-mixed fillers such as silica-acrylic composite particles (e.g., Soliostar manufactured by Nippon Shokubai); and composite fillers incorporating inorganic fine particles with organic materials. Among these, inorganic fillers are preferred, and among inorganic fillers, silica is preferred.

[0075] The filler (D) may be used alone or in combination of two or more types. If there are two or more types of filler (D), their combination and ratio can be selected arbitrarily.

[0076] In the thermosetting resin film (x1) and thermosetting resin composition (x1-1), when a filler (D) is used, the content of the filler (D) is preferably 5 to 50% by mass, more preferably 7 to 45% by mass, even more preferably 10 to 40% by mass, even more preferably 12 to 35% by mass, and still more preferably 15 to 25% by mass, based on the total amount of the active ingredient, from the viewpoint of adjusting the complex viscosity of the thermosetting resin film (x1) to an appropriate range and suppressing the peeling of the cured resin film from the chip due to thermal expansion and contraction.

[0077] The average particle size of the filler (D) is preferably 500 nm or less, more preferably 5 to 300 nm, and particularly preferably 10 to 100 nm. In this specification, the particle size of the filler (D) refers to the arithmetic mean particle size obtained by randomly selecting and measuring the particle sizes of multiple primary particles of the filler (D) observed with an electron microscope, and then calculating the average value of these measurements.

[0078] -Energy ray curable resin (E)- The thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may contain an energy ray curable resin (E). The thermosetting resin film (x1) contains an energy-ray curable resin (E), allowing its properties to be altered by irradiation with energy rays.

[0079] Energy-ray curable resin (E) is obtained by polymerizing (curing) an energy-ray curable compound. Examples of energy-ray curable compounds include a polymer (e1) having energy-ray curable groups and a weight-average molecular weight of 80,000 to 2,000,000, and a compound (e2) having energy-ray curable groups and a molecular weight of 100 to 80,000. The polymer (e1) may be at least partially crosslinked with a crosslinking agent, or it may not be crosslinked.

[0080] (A polymer (e1) having energy-ray curable groups and a weight-average molecular weight of 80,000 to 2,000,000) Examples of polymers (e1) having energy ray curable groups and a weight-average molecular weight of 80,000 to 2,000,000 include acrylic resins (e1-1) formed by an addition reaction between an acrylic polymer (e11) having a functional group that can react with a group of another compound, and an energy ray curable compound (e12) having a group that reacts with the functional group and an energy ray curable group such as an energy ray curable double bond.

[0081] Examples of functional groups that can react with groups of other compounds include hydroxyl groups, carboxyl groups, amino groups, substituted amino groups (groups in which one or two hydrogen atoms of an amino group are replaced by a group other than a hydrogen atom), and epoxy groups. However, in terms of preventing corrosion of circuits such as semiconductor wafers and semiconductor chips, it is preferable that the functional group is a group other than a carboxyl group. Among these, the functional group is preferably a hydroxyl group.

[0082] • Acrylic polymer having functional groups (e11) Examples of the acrylic polymer (e11) having the functional group include those obtained by copolymerizing an acrylic monomer having the functional group with an acrylic monomer not having the functional group, and those obtained by copolymerizing monomers other than acrylic monomers (non-acrylic monomers) in addition to these monomers. Furthermore, the acrylic polymer (e11) may be a random copolymer or a block copolymer.

[0083] Examples of acrylic monomers having the aforementioned functional groups include hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, substituted amino group-containing monomers, epoxy group-containing monomers, and the like.

[0084] Examples of the hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; and non-(meth)acrylic unsaturated alcohols such as vinyl alcohol and allyl alcohol (unsaturated alcohols that do not have a (meth)acryloyl skeleton).

[0085] Examples of the carboxyl group-containing monomers include ethylenically unsaturated monocarboxylic acids (monocarboxylic acids having an ethylenically unsaturated bond) such as (meth)acrylic acid and crotonic acid; ethylenically unsaturated dicarboxylic acids (dicarboxylic acids having an ethylenically unsaturated bond) such as fumaric acid, itaconic acid, maleic acid, and citraconic acid; anhydrides of the ethylenically unsaturated dicarboxylic acids; and carboxyalkyl esters of (meth)acrylic acid such as 2-carboxyethyl methacrylate.

[0086] The acrylic monomer having the aforementioned functional group is preferably a hydroxyl group-containing monomer or a carboxyl group-containing monomer, and more preferably a hydroxyl group-containing monomer.

[0087] The acrylic polymer (e11) may consist of only one acrylic monomer having the functional group, or two or more monomers. If there are two or more monomers, their combination and ratio can be arbitrarily selected.

[0088] Examples of acrylic monomers that do not have the aforementioned functional groups include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, and methyl (meth)acrylate. Examples of alkyl esters include isononyl, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl ((meth)acrylate) (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl ((meth)acrylate) (myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl ((meth)acrylate) (palmityl (meth)acrylate), heptadecyl (meth)acrylate, octadecyl ((meth)acrylate) (stearyl (meth)acrylate), etc., in which the alkyl group constituting the alkyl ester has a chain structure with 1 to 18 carbon atoms.

[0089] Furthermore, examples of acrylic monomers that do not have the aforementioned functional groups include alkoxyalkyl group-containing (meth)acrylic acid esters such as methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and ethoxyethyl (meth)acrylate; aromatic group-containing (meth)acrylic acid esters such as aryl (meth)acrylate such as phenyl (meth)acrylate; non-crosslinked (meth)acrylamide and its derivatives; and non-crosslinked (meth)acrylic acid esters having a tertiary amino group such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate.

[0090] The acrylic polymer (e11) may consist of only one acrylic monomer that does not have the functional group, or it may consist of two or more monomers. If there are two or more monomers, their combination and ratio can be arbitrarily selected.

[0091] Examples of the non-acrylic monomers include olefins such as ethylene and norbornene; vinyl acetate; and styrene. The non-acrylic monomers constituting the acrylic polymer (e11) may consist of only one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.

[0092] In the acrylic polymer (e11), the ratio (content) of the amount of constituent units derived from the functional group-containing acrylic monomer to the total amount of constituent units is preferably 0.1 to 50% by mass, more preferably 1 to 40% by mass, and particularly preferably 3 to 30% by mass. Having this ratio within this range allows the content of energy-ray-curable groups in the acrylic resin (e1-1) obtained by copolymerization of the acrylic polymer (e11) and the energy-ray-curable compound (e12) to easily adjust the degree of curing of the protective film within a preferred range.

[0093] The acrylic polymer (e11) constituting the acrylic resin (e1-1) may consist of only one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.

[0094] In the energy-ray curable resin (E), the content of the acrylic resin (e1-1) is preferably 1 to 40% by mass, more preferably 2 to 30% by mass, and particularly preferably 3 to 20% by mass.

[0095] • Energy ray curable compound (e12) The energy ray curable compound (e12) preferably has one or more groups selected from the group consisting of isocyanate groups, epoxy groups, and carboxyl groups as groups that can react with the functional groups of the acrylic polymer (e11), and more preferably has an isocyanate group as such. For example, if the energy ray curable compound (e12) has an isocyanate group as such, this isocyanate group readily reacts with the hydroxyl group of the acrylic polymer (e11) having a hydroxyl group as such as a functional group.

[0096] The energy ray curable compound (e12) preferably has 1 to 5 energy ray curable groups per molecule, and more preferably 1 to 2.

[0097] Examples of the energy-ray curable compound (e12) include 2-methacryloyloxyethyl isocyanate, meta-isopropenyl-α,α-dimethylbenzyl isocyanate, methacryloyl isocyanate, allyl isocyanate, and 1,1-(bisacryloyloxymethyl)ethyl isocyanate; Acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or polyisocyanate compound with hydroxyethyl (meth)acrylate; Examples include acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or polyisocyanate compound with a polyol compound and hydroxyethyl (meth)acrylate. Among these, the energy ray curable compound (e12) is preferably 2-methacryloyloxyethyl isocyanate.

[0098] The energy ray curable compound (e12) constituting the acrylic resin (e1-1) may consist of only one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.

[0099] In the acrylic resin (e1-1), the ratio of the content of energy-ray-curable groups derived from the energy-ray-curable compound (e12) to the content of the functional groups derived from the acrylic polymer (e11) is preferably 20 to 120 mol%, more preferably 35 to 100 mol%, and particularly preferably 50 to 100 mol%. Having the content within this range increases the adhesive strength of the protective film after curing. Note that if the energy-ray-curable compound (e12) is a monofunctional compound (having one of the groups in one molecule), the upper limit of the content ratio is 100 mol%, but if the energy-ray-curable compound (e12) is a polyfunctional compound (having two or more of the groups in one molecule), the upper limit of the content ratio may exceed 100 mol%.

[0100] The weight-average molecular weight (Mw) of the polymer (e1) is preferably 100,000 to 2,000,000, and more preferably 300,000 to 1,500,000. Here, "weight-average molecular weight" is as explained earlier.

[0101] If the polymer (e1) is crosslinked with a crosslinking agent in at least a portion thereof, the polymer (e1) may be a monomer that does not fall under any of the above-described monomers that constitute the acrylic polymer (e11) and has a group that reacts with the crosslinking agent, which is polymerized and crosslinked at the group that reacts with the crosslinking agent, or it may be a group that reacts with the functional group derived from the energy ray curable compound (e12).

[0102] The polymer (e1) contained in the thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may be one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.

[0103] (Compounds with energy-ray curable groups and a molecular weight of 100 to 80000 (e2)) Examples of energy-ray curable groups in compounds (e2) having a molecular weight of 100 to 80000 include groups containing energy-ray curable double bonds, and preferred examples include (meth)acryloyl groups and vinyl groups.

[0104] The compound (e2) is not particularly limited as long as it satisfies the above conditions, but examples include low molecular weight compounds having energy ray curable groups, epoxy resins having energy ray curable groups, and phenolic resins having energy ray curable groups.

[0105] Among the compounds (e2) mentioned above, examples of low molecular weight compounds having an energy-ray curable group include polyfunctional monomers or oligomers, and acrylate compounds having a (meth)acryloyl group are preferred. Examples of the acrylate compounds include 2-hydroxy-3-(meth)acryloyloxypropyl methacrylate, polyalkylene glycol (meth)acrylates such as polyethylene glycol di(meth)acrylate, propoxylated ethoxylated bisphenol E di(meth)acrylate, 2,2-bis[4-((meth)acryloxypolyethoxy)phenyl]propane, ethoxylated bisphenol A di(meth)acrylate, 2,2-bis[4-((meth)acryloxydiethoxy)phenyl]propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 2,2-bis[4-((meth)acryloxypolypropoxy)phenyl]propane, tricyclodecanedimethanol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 1,4-butylene glycoside. Difunctional (meth)acrylates such as di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 2,2-bis[4-(meth)acryloxyethoxy)phenyl]propane, neopentyl glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloxypropane, and dicyclopentanyl di(meth)acrylate; Tris(2-(meth)acryloxyethyl) isocyanurate, ε-caprolactone modified tris-(2-(meth)acryloxyethyl) isocyanurate, ethoxylated glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, ethoxylated pentaerythritol tetra( Polyfunctional (meth)acrylates such as meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; Oligoester (meth)acrylate; urethane (meth)acrylate oligomer; epoxy-modified (meth)acrylate; polyether (meth)acrylate other than the above polyalkylene glycol (meth)acrylate; Examples include polyfunctional (meth)acrylate oligomers such as urethane (meth)acrylate oligomers; and itaconic acid oligomers. Furthermore, the acrylate compound may be, for example, a chain-like aliphatic skeleton-containing (meth)acrylate such as trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate; a cyclic aliphatic skeleton-containing (meth)acrylate such as dicyclopentanyl di(meth)acrylate; and the like.

[0106] Of the compounds (e2) mentioned above, epoxy resins having energy-ray curable groups and phenolic resins having energy-ray curable groups may also be resins constituting thermosetting component (B), but in the present invention they are treated as compounds (e2).

[0107] The compound (e2) preferably has a weight-average molecular weight of 100 to 30,000, and more preferably 300 to 10,000.

[0108] The compound (e2) contained in the thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may be one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.

[0109] The energy-curable compounds used in polymerization may be used individually or in combination of two or more. When two or more energy-curable compounds are used in polymerization, their combination and ratio can be arbitrarily selected. For example, the polymer (e1) and the compound (e2) may be used individually or in combination.

[0110] In thermosetting resin films (x1) and thermosetting resin compositions (x1-1), when an energy-ray curable resin (E) is used, the content of the energy-ray curable resin (E) is preferably 1 to 95% by mass, more preferably 5 to 90% by mass, and even more preferably 10 to 85% by mass, based on the total amount of active ingredients in the thermosetting resin composition (x1-1).

[0111] -Photopolymerization initiator (F)- If the thermosetting resin film (x1) and thermosetting resin composition (x1-1) contain an energy ray curable resin (E), the thermosetting resin film (x1) and thermosetting resin composition (x1-1) may contain a photopolymerization initiator (F) in order to efficiently advance the polymerization reaction of the energy ray curable resin (E).

[0112] Examples of photopolymerization initiators (F) include benzophenone, acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin methyl benzoate, benzoin dimethyl ketal, 2,4-diethylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, benzyl diphenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, benzyl, dibenzyl, diacetyl, 1,2-diphenylmethane, 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 2-chloroanthraquinone.

[0113] The photopolymerization initiator (F) may be used alone or in combination of two or more types. If there are two or more types of photopolymerization initiator (F), their combination and ratio can be arbitrarily selected.

[0114] In the thermosetting resin film (x1) and thermosetting resin composition (x1-1), when a photopolymerization initiator (F) is used, the content of the photopolymerization initiator (F) is preferably 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 2 to 5 parts by mass, based on 100 parts by mass of the energy ray curable resin (E).

[0115] -Additive (G)- The thermosetting resin film (x1) and the thermosetting resin composition (x1-1) may contain additive (G) as long as the effects of the present invention are not impaired. Additive (G) may be any known additive and can be arbitrarily selected depending on the purpose, and is not particularly limited. Preferred additives (G) include, for example, rheology control agents, coupling agents, crosslinking agents, surfactants, plasticizers, antistatic agents, antioxidants, leveling agents, gettering agents, and silicone oils.

[0116] Additive (G) may be used alone or in combination of two or more types. If there are two or more types of additive (G), their combination and ratio can be arbitrarily selected. The amount of additive (G) is not particularly limited and should be selected as appropriate depending on the purpose.

[0117] -solvent- The thermosetting resin composition (x1-1) preferably further contains a solvent. A thermosetting resin composition (x1-1) containing a solvent has good handling properties. The solvent is not particularly limited, but preferred solvents include, for example, hydrocarbons such as toluene and xylene; alcohols such as methanol, ethanol, 2-propanol, isobutyl alcohol (2-methylpropan-1-ol), and 1-butanol; esters such as ethyl acetate; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; and amides (compounds having an amide bond) such as dimethylformamide and N-methylpyrrolidone. The solvent may be used alone or in combination of two or more types. If two or more solvents are used, their combination and ratio can be arbitrarily selected. The solvent is preferably methyl ethyl ketone or the like, as it allows for more uniform mixing of the components contained in the thermosetting resin composition (x1-1).

[0118] -Method for preparing a thermosetting resin composition (x1-1)- A thermosetting resin composition (x1-1) is prepared by blending the components that make it up. The order in which each component is added during formulation is not particularly limited, and two or more components may be added simultaneously. When using a solvent, the solvent may be used after pre-diluting the formulation by mixing it with any of the other components, or the solvent may be used by mixing it with the other components without pre-diluting them. The method of mixing each component during formulation is not particularly limited; it can be appropriately selected from known methods such as mixing by rotating a stirring bar or impeller, mixing using a mixer, or mixing by applying ultrasonic waves. The temperature and time during the addition and mixing of each component are not particularly limited as long as the components do not deteriorate, and can be adjusted as appropriate, but a temperature of 15 to 30°C is preferred.

[0119] (Composition of energy ray curable resin film (x2)) The energy ray-curable resin film (x2) contains an energy ray-curable component (α). The energy ray-curable resin film (x2) is formed from, for example, an energy ray-curable resin composition (x2-1) containing an energy ray-curable component (α). The energy ray curable component (α) is preferably uncured, more preferably tacky, and even more preferably both uncured and tacky. In this specification, the following description of "the content of each component on a total basis of the active ingredients of the energy ray-curable resin composition (x2-1)" is synonymous with "the content of each component of the energy ray-curable resin film (x2) formed from the energy ray-curable resin composition (x2-1)".

[0120] (Energy ray curing component (α)) The energy ray curable component (α) is a component that hardens upon irradiation with energy rays, and is also a component that imparts film-forming properties and flexibility to the energy ray curable resin film (x2). Examples of the energy-ray curable component (α) include a polymer (α1) having an energy-ray curable group and a weight-average molecular weight of 80,000 to 2,000,000, and a compound (α2) having an energy-ray curable group and a molecular weight of 100 to 80,000. The polymer (α1) may be at least partially crosslinked with a crosslinking agent, or it may not be crosslinked.

[0121] Furthermore, the polymer (α1) and compound (α2) in the energy-ray curable resin composition (x2-1) are the same as the polymer (e1) and compound (e2) in the thermosetting resin composition (x1-1), and their preferred embodiments are also the same as those of the polymer (e1) and compound (e2) in the thermosetting resin composition (x1-1).

[0122] (Polymer (β) without energy-ray curable groups) When the energy-ray curable resin composition (x2-1) and the energy-ray curable resin film (x2) contain compound (α2) as the energy-ray curable component (α), it is preferable that they also contain a polymer (β) that does not have an energy-ray curable group. The polymer (β) that does not have energy-ray curable groups may be crosslinked with a crosslinking agent in at least a portion of it, or it may not be crosslinked.

[0123] Examples of polymers (β) that do not have energy-ray curable groups include acrylic polymers, phenoxy resins, urethane resins, polyesters, rubber resins, acrylic urethane resins, and polyvinyl acetals. Among these, polymers (β) are preferably acrylic polymers (hereinafter sometimes abbreviated as "acrylic polymer (β-1)") and polyvinyl acetals.

[0124] The acrylic polymer (β-1) may be any known polymer, for example, a homopolymer of one acrylic monomer, or a copolymer of two or more acrylic monomers. Alternatively, the acrylic polymer (β-1) may be a copolymer of one or more acrylic monomers and one or more monomers other than acrylic monomers (non-acrylic monomers).

[0125] Examples of the acrylic monomers constituting the acrylic polymer (β-1) include alkyl (meth)acrylates, (meth)acrylates having a cyclic skeleton, glycidyl group-containing (meth)acrylates, hydroxyl group-containing (meth)acrylates, and substituted amino group-containing (meth)acrylates.

[0126] Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, and isono(meth)acrylate. Examples of alkyl esters include (meth)acrylates such as nyl, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl ((meth)acrylate) (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl ((meth)acrylate) (myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl ((meth)acrylate) (palmityl (meth)acrylate), heptadecyl (meth)acrylate, and octadecyl ((meth)acrylate) (stearyl (meth)acrylate), in which the alkyl group constituting the alkyl ester has a chain structure with 1 to 18 carbon atoms.

[0127] Examples of (meth)acrylic acid esters having a cyclic skeleton include cycloalkyl (meth)acrylate esters such as isobornyl (meth)acrylate and dicyclopentanyl (meth)acrylate; aralkyl (meth)acrylate esters such as benzyl (meth)acrylate; cycloalkenyl (meth)acrylate esters such as dicyclopentenyl (meth)acrylate; and cycloalkenyloxyalkyl (meth)acrylate esters such as dicyclopentenyloxyethyl (meth)acrylate.

[0128] Examples of glycidyl group-containing (meth)acrylic acid esters include glycidyl (meth)acrylate. Examples of hydroxyl group-containing (meth)acrylic acid esters include hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Examples of the substituted amino group-containing (meth)acrylic acid ester include N-methylaminoethyl (meth)acrylic acid.

[0129] Examples of non-acrylic monomers that constitute the acrylic polymer (β-1) include olefins such as ethylene and norbornene; vinyl acetate; and styrene.

[0130] As for the polyvinyl acetal, as explained in the section on polymer component (A), polyvinyl formal and polyvinyl butyral are preferred, with polyvinyl butyral being more preferred. Furthermore, as for the polyvinyl butyral, those having the constituent units represented by the above formulas (i)-1, (i)-2, and (i)-3 are preferred. The preferred embodiments of polyvinyl butyral are as described in polymer component (A), and the explanation is omitted.

[0131] Examples of polymers (β) that do not have energy-ray curable groups and are crosslinked by a crosslinking agent include polymers (β) in which reactive functional groups react with the crosslinking agent. The reactive functional group can be appropriately selected depending on the type of crosslinking agent, etc., and is not particularly limited. For example, when the crosslinking agent is a polyisocyanate compound, the reactive functional group can be a hydroxyl group, a carboxyl group, or an amino group, and among these, the hydroxyl group, which has high reactivity with the isocyanate group, is preferred. Furthermore, when the crosslinking agent is an epoxy compound, the reactive functional group can be a carboxyl group, an amino group, or an amide group, and among these, the carboxyl group, which has high reactivity with epoxy groups, is preferred. However, in terms of preventing corrosion of the circuit surface of the soldered wiring board, it is preferable that the reactive functional group is a group other than a carboxyl group.

[0132] Examples of polymers (β) having reactive functional groups but not energy-ray curable groups include those obtained by polymerizing monomers having at least reactive functional groups. In the case of acrylic polymers (β-1), either or both of the acrylic and non-acrylic monomers listed as constituent monomers may have reactive functional groups. For example, an example of a polymer (β) having a hydroxyl group as a reactive functional group is one obtained by polymerizing a hydroxyl group-containing (meth)acrylic acid ester. In addition, polymers obtained by polymerizing monomers in which one or more hydrogen atoms are substituted with the reactive functional group in the aforementioned acrylic or non-acrylic monomers may also be used.

[0133] In a polymer (β) having a reactive functional group, the ratio (content) of the amount of constituent units derived from the monomer having a reactive functional group to the total mass of the constituent units is preferably 1 to 20% by mass, and more preferably 2 to 10% by mass. When the ratio is within this range, the degree of crosslinking in polymer (β) is within a more preferable range.

[0134] The weight-average molecular weight (Mw) of the polymer (β) that does not have energy-ray curable groups is preferably 10,000 to 2,000,000, and more preferably 20,000 to 1,500,000, from the viewpoint that the film-forming properties of the energy-ray curable resin composition (x2-1) will be better.

[0135] The polymer (β) that does not have energy-ray curable groups may be used alone or in combination of two or more types. When there are two or more polymers (β) that do not have energy-ray curable groups, their combination and ratio can be arbitrarily selected.

[0136] Examples of energy-ray curable resin compositions (x2-1) include those containing either or both of the polymer (α1) and the compound (α2). Furthermore, if the energy-ray curable resin composition (x2-1) contains compound (α2), it is preferable that it also contains a polymer (β) that does not have an energy-ray curable group, and in this case, it is also preferable that it contains polymer (α1). Furthermore, the energy-ray curable resin composition (x2-1) may not contain compound (α2) and may contain both polymer (α1) and polymer (β) that does not have an energy-ray curable group.

[0137] When the energy-ray curable resin composition (x2-1) contains a polymer (α1), a compound (α2), and a polymer (β) that does not have an energy-ray curable group, the content of compound (α2) is preferably 10 to 400 parts by mass, and more preferably 30 to 350 parts by mass, based on 100 parts by mass of the total content of polymer (α1) and polymer (β) that does not have an energy-ray curable group.

[0138] The total content of the energy ray-curable component (α) and the polymer (β) without energy ray-curable groups is preferably 5 to 90% by mass, more preferably 10 to 80% by mass, and even more preferably 20 to 70% by mass, based on the total amount of active ingredients in the energy ray-curable resin composition (x2-1). Having the energy ray-curable component content within this range results in better energy ray curability of the energy ray-curable resin film (x2).

[0139] The energy-ray curable resin composition (x2-1) may contain, in addition to the energy-ray curable component, one or more components selected from the group consisting of thermosetting components, photopolymerization initiators, fillers, coupling agents, crosslinking agents, and additives, depending on the purpose. For example, by using an energy-ray curable resin composition (x2-1) containing an energy-ray curable component and a thermosetting component, the energy-ray curable resin film (x2) formed has improved adhesion to the adherend upon heating, and the strength of the cured resin film formed from this energy-ray curable resin film (x2) is also improved.

[0140] The thermosetting component, photopolymerization initiator, and additive in the energy ray curable resin composition (x2-1) are the same as those in the thermosetting component (B), photopolymerization initiator (F), filler (D), and additive (G) in the thermosetting resin composition (x1-1), respectively.

[0141] In the energy-ray curable resin composition (x2-1), the thermosetting component, photopolymerization initiator, filler, and additive may each be used individually or in combination of two or more. When two or more are used in combination, the combination and ratio can be arbitrarily selected. The content of thermosetting components, photopolymerization initiators, fillers, and additives in the energy ray curable resin composition (x2-1) can be adjusted as appropriate depending on the purpose, and is not particularly limited.

[0142] The energy-ray curable resin composition (x2-1) is preferable to further contain a solvent, as its handling properties are improved by dilution. Examples of solvents contained in the energy-ray-curable resin composition (x2-1) include the same solvent as that in the thermosetting resin composition (x1-1). The solvent contained in the energy-ray curable resin composition (x2-1) may be used alone or in combination of two or more types. When using two or more types in combination, the combination and ratio can be arbitrarily selected.

[0143] (Other ingredients) The energy-ray curable resin composition (x2-1) may contain, in addition to the energy-ray curable component described above, appropriate amounts of components other than the curable component, namely curing accelerators (C), fillers (D), additives (G), etc., similar to the case of the thermosetting resin film (x1) described earlier.

[0144] (Method for preparing an energy-ray curable resin composition (x2-1)) The energy-ray curable resin composition (x2-1) is obtained by blending the components that constitute it. The order in which the components are added is not particularly limited, and two or more components may be added simultaneously. When using a solvent, the solvent may be used after pre-diluting the mixture by mixing it with any of the other components, or the solvent may be used by mixing it with the other components without pre-diluting them. The method of mixing each component during formulation is not particularly limited, and any known method may be appropriately selected, such as mixing by rotating a stirring bar or impeller; mixing using a mixer; or mixing by applying ultrasound. The temperature and time during the addition and mixing of each component are not particularly limited as long as the components do not deteriorate, and can be adjusted as appropriate, but a temperature of 15 to 30°C is preferred.

[0145] (Preparation of a heat-fluid curable resin film (x)) A thermofluidly curable resin film (x) can be manufactured, for example, by coating the surface to be formed with a curable resin composition such as the thermosetting resin composition (x1-1) or the energy ray curable resin composition (x2-1) of this embodiment (hereinafter also referred to as "curable resin composition (x-1)") and drying it as necessary. The curable resin composition (x-1) can be applied by known methods, such as using various coaters including an air knife coater, blade coater, bar coater, gravure coater, roll coater, roll knife coater, curtain coater, die coater, knife coater, screen coater, Meyer bar coater, and kiss coater. The drying conditions after applying the curable resin composition (x-1) are not particularly limited, but for example, the drying temperature can be set to 70 to 130°C and the drying time to 10 seconds to 5 minutes.

[0146] [Configuration of the thermofluid-curable resin film composite sheet of this embodiment] The heat-fluidable curable resin film (x) of this embodiment may be a single-layer film or may be formed on the release surface of a release film, but from the viewpoint of improving handling and other aspects, it is preferable that it be a composite sheet with a support sheet. The following describes the configuration examples of the composite sheet of this embodiment, specifically the first to third embodiments. However, the configuration examples of the composite sheet of this embodiment are not limited to the first to third embodiments. For example, the first to third embodiments may of course have other layers, as long as they do not significantly impair the effects of the present invention.

[0147] (First aspect) Figure 1 shows a first embodiment of the composite sheet of this embodiment. The composite sheet 1a shown in Figure 1 comprises a base material 10 and a heat-fluidable curable resin film (x). In the first embodiment, the support sheet is the base material 10. Although not shown, a release film or the like may be provided on the side of the heat-fluidable curable resin film (x) opposite to the base material 10.

[0148] (Second aspect) A second embodiment of the composite sheet of this embodiment is shown in Figure 2. The composite sheet 1b shown in Figure 2 has a base material 10, an intermediate layer 11, and a heat-fluidable curable resin film (x) in that order. In the second embodiment, the support sheet is a laminate of the base material 10 and the intermediate layer 11. Although not shown, a release film or the like may be provided on the side of the heat-fluidable curable resin film (x) opposite to the intermediate layer 11.

[0149] (Third aspect) A third embodiment of the composite sheet of this embodiment is shown in Figure 3. The composite sheet 1c of the third embodiment has an intermediate release layer between the intermediate layer 11 and the heat-fluid curable resin film (x) in the composite sheet of the second embodiment. That is, as shown in Figure 3, the composite sheet 1c of the third embodiment has a base material 10, an intermediate layer 11 laminated on one side 10a of the base material 10, an intermediate release layer 13 laminated on the side of the intermediate layer 11 opposite to the base material 10, and a heat-fluid curable resin film (x) laminated on the side of the intermediate release layer 13 opposite to the intermediate layer 11. In the second embodiment, the support sheet is a laminate of the base material 10, the intermediate layer 11, and the intermediate release layer 13. Although not shown, a release film or the like may be provided on the side of the heat-fluid curable resin film (x) opposite to the intermediate release layer 13.

[0150] (Middle class) As described above, the composite sheet of this embodiment may have an intermediate layer between the substrate and the heat-fluidable curable resin film (x). The intermediate layer is a layer that has a buffering effect against forces applied to the intermediate layer and the layers directly or indirectly adjacent to it. Here, "layers directly or indirectly adjacent to the intermediate layer" mainly refers to the heat-fluidable curable resin film (x) of this embodiment.

[0151] The intermediate layer may consist of only one layer or two or more layers. If there are multiple intermediate layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.

[0152] The thickness of the intermediate layer can be adjusted as appropriate according to the surface irregularities of the member, but from the viewpoint of making it easier to exert the effects of the present invention even when relatively high protrusions are provided, it is preferably 100 to 1,000 μm, more preferably 120 to 800 μm, and even more preferably 150 to 500 μm.

[0153] -Storage modulus (G') of the intermediate layer at 80°C- In the composite sheet of this embodiment, the storage modulus (G') of the intermediate layer at 80°C is preferably 0.08 MPa or higher. If the storage modulus (G') of the intermediate layer at 80°C is 0.08 MPa or higher, it becomes easier to ensure that the heat-fluidable curable resin film (x) can be embedded into the irregularities on the circuit-forming surface (α) of the component. Here, from the viewpoint of making it easier to ensure the embedding of the heat-fluidable curable resin film (x) into the irregularities on the circuit-forming surface (α) of the component, the storage modulus (G') of the intermediate layer at 80°C is more preferably 0.10 MPa or higher, even more preferably 0.12 MPa or higher, even more preferably 0.14 MPa or higher, and still more preferably 0.16 MPa or higher. Furthermore, the storage modulus (G') of the intermediate layer at 80°C is preferably 0.4 MPa or less, from the viewpoint of making it easier to adjust the loss tangent (tanδ) of the intermediate layer at 80°C, which will be described later, to 1.02 or more, and thus making it easier to ensure the embedding ability of the heat-fluidable curable resin film (x) into the irregularities on the circuit-forming surface (α) of the member.

[0154] -Loss tangent (tanδ) of the interlayer at 80°C- In the composite sheet of this embodiment, the loss tangent (tanδ) of the intermediate layer at 80°C is preferably 1.02 or greater. If the loss tangent (tanδ) of the intermediate layer at 80°C is 1.02 or higher, it is easier to ensure that the heat-fluidable curable resin film (x) can be embedded into the irregularities on the circuit-forming surface (α) of the component. Here, from the viewpoint of making it easier to ensure the embedding of the heat-fluidable curable resin film (x) into the irregularities on the circuit-forming surface (α) of the component, the loss tangent (tanδ) of the intermediate layer at 80°C is more preferably 1.05 or higher, even more preferably 1.08 or higher, even more preferably 1.12 or higher, and still more preferably 1.16 or higher. Furthermore, the loss tangent (tanδ) of the intermediate layer at 80°C is preferably 2.00 or less, from the viewpoint of making it easier to adjust the storage modulus (G') of the intermediate layer at 80°C to 0.08 or higher, thereby ensuring the embedding ability of the heat-fluidable curable resin film (x) into uneven surfaces.

[0155] The storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be measured, for example, by the following method. The sample size to be measured is 8 mm in diameter and 1 mm thick (5 layers of 200 μm intermediate layers stacked together). Using a rheometer (Anton Paar MCR302), the sample, with the release film removed, is sandwiched between parallel plates from above and below. Shear stress is applied to the sample at a measurement temperature of 0 to 100 °C, a gap of 1 mm, a strain of 0.05 to 0.5%, and an angular frequency of 1 Hz, and the shear storage modulus G' and loss tangent tanδ at 80 °C are calculated.

[0156] In this embodiment, the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be appropriately adjusted by adjusting the composition of the intermediate layer, etc. The following describes the details of the composition of the intermediate layer, taking into account the methods for adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C.

[0157] -Urethane (meth)acrylate- Urethane (meth)acrylate is a compound having at least a (meth)acryloyl group and a urethane bond, and has the property of polymerizing upon energy ray irradiation. By using urethane (meth)acrylate, flexibility can be provided to the intermediate layer, and the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be easily adjusted to the above range. The urethane (meth)acrylate may be monofunctional or polyfunctional. In this embodiment, polyfunctional urethane (meth)acrylate is preferred, and bifunctional urethane (meth)acrylate is preferred from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range. The urethane (meth)acrylate may be an oligomer, a polymer, or a mixture thereof. In this embodiment, a urethane (meth)acrylate oligomer is preferred. Urethane (meth)acrylate can be obtained, for example, by reacting a terminal isocyanate urethane prepolymer, which is obtained by reacting a polyol compound with a polyvalent isocyanate compound, with a (meth)acrylate having a hydroxyl group. Note that one or more types of urethane (meth)acrylate may be used. The content of urethane (meth)acrylate in the intermediate layer-forming composition is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range. Furthermore, the content of urethane (meth)acrylate in the intermediate layer composition is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 50% by mass or less.

[0158] -Polymerizable monomer- The polymerizable monomer is preferably a polymerizable compound other than the urethane (meth)acrylate mentioned above, and is a compound that can be polymerized with other components by irradiation with energy rays. Specifically, the polymerizable monomer is preferably a compound having at least one (meth)acryloyl group. Examples of polymerizable monomers include (meth)acrylates having alkyl groups with 1 to 30 carbon atoms; (meth)acrylates having functional groups such as hydroxyl groups, amide groups, amino groups, and epoxy groups; (meth)acrylates having an alicyclic structure; (meth)acrylates having an aromatic structure; (meth)acrylates having a heterocyclic structure; and vinyl compounds such as styrene, hydroxyethyl vinyl ether, hydroxybutyl vinyl ether, N-vinylformamide, N-vinylpyrrolidone, and N-vinylcaprolactam. Examples of (meth)acrylates having alkyl groups with 1 to 30 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, and eicosyl (meth)acrylate. Examples of functional group-containing (meth)acrylates include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-methylol (meth)acrylamide. Examples include amide group-containing compounds such as lylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide; amino group-containing (meth)acrylates such as primary amino group-containing (meth)acrylates, secondary amino group-containing (meth)acrylates, and tertiary amino group-containing (meth)acrylates; and epoxy group-containing (meth)acrylates such as glycidyl(meth)acrylate, methylglycidyl(meth)acrylate, and allylglycidyl ether. Examples of (meth)acrylates having an alicyclic structure include isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, and adamantane (meth)acrylate. Examples of (meth)acrylates having an aromatic structure include phenylhydroxypropyl (meth)acrylate, benzyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate. Examples of (meth)acrylates having a heterocyclic structure include tetrahydrofurfuryl(meth)acrylate and morpholine(meth)acrylate. In this embodiment, the polymerizable monomer preferably includes (meth)acrylates having an alkyl group with 1 to 30 carbon atoms and (meth)acrylates having an alicyclic structure. From the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range, (meth)acrylates having an alkyl group with 4 to 14 carbon atoms are preferred, and as (meth)acrylates having an alicyclic structure, isobornyl (meth)acrylate and trimethylcyclohexyl (meth)acrylate are preferred. Furthermore, if the intermediate layer-forming composition contains a crosslinking agent, (meth)acrylates having functional groups that can react with the crosslinking agent are undesirable. This is because the crosslinked structure formed by the crosslinking reaction may increase the residual stress of the intermediate layer. For example, an intermediate layer-forming composition containing a polyisocyanate-based crosslinking agent and a (meth)acrylate having hydroxyl groups is undesirable. The content of polymerizable monomers in the intermediate layer forming composition is preferably 20% by mass or more, and more preferably 30% by mass or more, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range. Furthermore, the content of polymerizable monomers in the intermediate layer forming composition is preferably 80% by mass or less, and more preferably 70% by mass or less. Furthermore, the mass ratio of urethane (meth)acrylate to polymerizable monomer (urethane (meth)acrylate / polymerizable monomer) in a total of 100 parts by mass of urethane (meth)acrylate and polymerizable monomer is preferably 20 / 80 to 80 / 20, and more preferably 30 / 70 to 70 / 30, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range.

[0159] -Photopolymerization initiator- When the intermediate layer forming composition contains the above-mentioned urethane (meth)acrylate and polymerizable monomer, it is preferable that the intermediate layer forming composition also contains a photopolymerization initiator. By including a photopolymerization initiator, polymerization proceeds reliably, and the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be easily adjusted to the above range. Examples of photopolymerization initiators include benzoin compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, thioxanthone compounds, and peroxide compounds, as well as photosensitizers such as amines and quinones. Specifically, examples include 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. These photopolymerization initiators may be used individually or in combination of two or more. The amount of photopolymerization initiator added is preferably 0.05 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the total of urethane (meth)acrylate and polymerizable monomer.

[0160] -Chain Transfer Agent- The intermediate layer forming composition preferably contains a chain transfer agent. The chain transfer agent can induce a chain transfer reaction and regulate the progress of the curing reaction of the intermediate layer forming composition. By including a chain transfer agent, components with relatively short molecular chains can remain even after curing, so that the cured polymer has a relatively flexible structure. As a result, the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be easily adjusted to the above range. Examples of chain transfer agents include thiol group-containing compounds. Examples of thiol group-containing compounds include nonyl mercaptan, 1-dodecanethiol, 1,2-ethanedithiol, 1,3-propanedithiol, triazinethiol, triazinedithiol, triazinetrithiol, 1,2,3-propanetrithiol, tetraethylene glycol-bis(3-mercaptopropionate), trimethylolpropanetris(3-mercaptopropionate), pentaerythritoltetrakis(3-mercaptopropionate), and pentaerythritol. Examples include thritol tetrakisthioglucolate, dipentaerythritol hexakis(3-mercaptopropionate), tris[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), and 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione. The chain transfer agent may be used individually or in combination of two or more types. From the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C to the above range, the amount of chain transfer agent is preferably 1.0 to 2.5 parts by mass, more preferably 1.2 to 2.0 parts by mass, and even more preferably 1.3 to 1.8 parts by mass, per 100 parts by mass of the total of urethane (meth)acrylate and polymerizable monomer.

[0161] -Other ingredients- The intermediate layer may contain other components. These other components are not particularly limited and can be appropriately selected depending on the purpose.

[0162] - Fabrication of the intermediate layer - As a composition for forming the intermediate layer, for example, an intermediate layer-forming composition containing the above-mentioned components, or a composition obtained by diluting the intermediate layer-forming composition with a solvent or the like, can be prepared. Examples of solvents include organic solvents such as methyl ethyl ketone, acetone, ethyl acetate, tetrahydrofuran, dioxane, cyclohexane, n-hexane, toluene, xylene, n-propanol, and isopropanol. Then, an intermediate layer-forming composition is applied to a release film or substrate by a known method such as spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, or gravure coating to form a coating film, and this coating film is cured to form an intermediate layer on the substrate. In this embodiment, it is preferable to cure the coating film by irradiation with energy rays. Examples of energy rays include ultraviolet rays and electron beams, with ultraviolet rays being preferred. Furthermore, in this embodiment, it is preferable to cure the coating film by irradiating it with energy rays multiple times. By doing so, the degree of curing of the intermediate layer can be controlled, and the storage modulus (G') and loss tangent (tanδ) of the intermediate layer at 80°C can be easily adjusted to the above range. If the energy source is ultraviolet light, the ultraviolet irradiation conditions are preferably such that the ultraviolet irradiance is 30-500 mW / cm². 2 More preferably 50-340 mW / cm² 2 The ultraviolet radiation dose (cumulative light dose) is preferably 100 to 2,500 mJ / cm². 2 More preferably 150 to 2,000 mJ / cm² 2 That is the case. When irradiating with ultraviolet light multiple times, it is preferable that the illuminance and irradiation dose are greater than those of the previous irradiation. Alternatively, the coated film may be exposed to oxygen and irradiated with energy rays, and then the coated film may be shielded from oxygen and irradiated with energy rays again.

[0163] (Intermediate delamination layer) As described above, the composite sheet of this embodiment may have an intermediate release layer between the intermediate layer and the thermofluid-curable resin film (x). The intermediate release layer is provided to easily peel the support sheet from the thermofluid-curable resin film (x) after the thermofluid-curable resin film (x) has been attached to the circuit-forming surface (α) of the member, and does not need to be provided if it is easy to peel the support sheet from the thermofluid-curable resin film (x).

[0164] The intermediate delamination layer is in the form of a sheet or film, and its constituent material is not particularly limited. The intermediate peeling layer may contain, for example, a (meth)acrylic acid ester polymer or an ethylene vinyl acetate copolymer (EVA), but it is preferable that it contains an ethylene-vinyl acetate copolymer (EVA). The intermediate peeling layer may contain other components besides those mentioned above. These other components are not particularly limited and can be appropriately selected depending on the purpose.

[0165] The interdebris layer may be a single layer or a multi-layer structure of two or more layers. If the interdebris layer consists of multiple layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.

[0166] The thickness of the interlayer is not particularly limited, but is preferably 5 to 30 μm, more preferably 6 to 25 μm, and even more preferably 7 to 20 μm.

[0167] (base material) The base material is in the form of a sheet or film, and its constituent materials include, for example, the following various resins. Examples of resins constituting the base material include polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE); polyolefins other than polyethylene such as polypropylene, polybutene, polybutadiene, polymethylpentene, and norbornene resin; ethylene-based copolymers such as ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, and ethylene-norbornene copolymer (polymers obtained using ethylene as a monomer); and vinyl chloride-based resins such as polyvinyl chloride and vinyl chloride copolymer (using vinyl chloride as a monomer). Examples of resins obtained from this process include: polystyrene; polycycloolefin; polyesters such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene isophthalate, polyethylene-2,6-naphthalenedicarboxylate, and all aromatic polyesters having aromatic cyclic groups as all constituent units; copolymers of two or more of the above polyesters; poly(meth)acrylic acid esters; polyurethane; polyurethane acrylate; polyimide; polyamide; polycarbonate; fluororesin; polyacetal; modified polyphenylene oxide; polyphenylene sulfide; polysulfone; polyether ketone; and the like. Furthermore, examples of resins constituting the base material include polymer alloys such as mixtures of the above-mentioned polyester and other resins. It is preferable that the polymer alloy of polyester and other resins contains a relatively small amount of the resin other than polyester. Furthermore, examples of resins constituting the base material include crosslinked resins obtained by crosslinking one or more of the above-mentioned resins; and modified resins such as ionomers using one or more of the above-mentioned resins. The resins that make up the base material may be used individually or in combination of two or more types.

[0168] The base material may consist of only one layer or two or more layers. If the base material consists of multiple layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.

[0169] The thickness of the substrate is not particularly limited, but is preferably 5 to 1,000 μm, more preferably 10 to 500 μm, even more preferably 15 to 300 μm, and even more preferably 20 to 150 μm.

[0170] The base material is preferably one with high thickness accuracy, that is, one in which thickness variation is suppressed regardless of the location. Among the constituent materials mentioned above, examples of materials with high thickness accuracy that can be used to construct such a base material include polyethylene, polyolefins other than polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyesters other than polyethylene terephthalate and polybutylene terephthalate, and ethylene-vinyl acetate copolymers.

[0171] In addition to the main constituent materials such as the resin mentioned above, the base material may also contain various known additives such as fillers, colorants, antioxidants, organic lubricants, catalysts, and plasticizers.

[0172] The substrate may be transparent or opaque, may be colored depending on the purpose, or may have other layers deposited on it. Furthermore, if the heat-fluidable curable resin film (x) has energy ray curability, it is preferable that the substrate is one that transmits energy rays.

[0173] The substrate can be manufactured by known methods. For example, a substrate containing a resin can be manufactured by molding a resin composition containing the above-mentioned resin.

[0174] (Method of manufacturing composite sheets) The composite sheet of this embodiment can be manufactured by sequentially stacking the above-mentioned layers in corresponding positional relationships. For example, a composite sheet having a laminated structure of a substrate and a heat-fluidable curable resin film (x) can be manufactured by the method shown below. The curable resin composition (x-1) of this embodiment is applied to the release surface of the release film, and a heat-fluid curable resin film (x) is formed on the release film by drying as necessary. Next, the substrate and the exposed surface of the heat-fluidable curable resin film (x) opposite to the release film are bonded together. This yields a composite sheet having a laminated structure of the substrate and the heat-fluidable curable resin film (x). The release film provided on the heat-fluidable curable resin film (x) in the composite sheet can be removed at any stage between the time of manufacture of the composite sheet and the time of use. Furthermore, a composite sheet having a laminated structure of a substrate and a heat-fluidable curable resin film (x) can also be manufactured by coating one side of the substrate with a curable resin composition (x-1) and drying it as necessary.

[0175] Furthermore, for example, a composite sheet having a base material, an intermediate layer, and a heat-fluidable curable resin film (x) in this order can be manufactured by the method shown below. An intermediate layer is formed on a release film by coating one surface of a substrate with an intermediate layer-forming composition and curing it. A first laminated sheet is obtained by laminating the substrate and the intermediate layer. A release film may be provided on the surface of the intermediate layer in the first laminated sheet opposite to the substrate, if necessary. Separately, the curable resin composition (x-1) of this embodiment is applied to the release surface of the release film and dried as necessary to form the curable resin composition (x-1) on the release film. Next, the exposed surface of the intermediate layer of the first laminated sheet opposite to the substrate is bonded to the exposed surface of the heat-fluidable curable resin film (x) opposite to the release film. This results in a composite sheet having a structure in which the substrate, intermediate layer, heat-fluidable curable resin film (x), and release film are laminated in this order. The release film provided on the heat-fluidable curable resin film (x) in the composite sheet can be removed at any stage between the time of manufacture of the composite sheet and the time of use.

[0176] A composite sheet comprising layers other than those described above can be manufactured by adding or omitting steps as appropriate in the manufacturing method described above, so that the stacking positions of each layer are at the desired positions. The same applies to the modified forms of the composite sheet described later.

[0177] (Variations of composite sheets) Examples of modified composite sheets include a composite sheet comprising a backgrind sheet and a heat-fluidable curable resin film (x) laminated on the adhesive surface of the backgrind sheet.

[0178] <Background Grind Sheet> As previously mentioned, the backgrind sheet is attached to the circuit formation surface during back-side grinding of semiconductor wafers to protect that surface.

[0179] [Configuration of the backgrind sheet in this embodiment] The following describes the configuration of the backgrind sheet of this embodiment, specifically the first and second embodiments. However, the configuration of the backgrind sheet of this embodiment is not limited to the first and second embodiments. For example, in the first and second embodiments, other layers may be included as long as they do not significantly impede the effects of the present invention. For instance, an intermediate layer may be included between the substrate and the adhesive layer.

[0180] (First aspect) A first embodiment of the backgrind sheet of this embodiment is shown in Figures 4(a) and (b). The backgrind sheet 2a shown in Figure 4(a) has a base material 30 and an adhesive layer 31a. The backgrind sheet 2b shown in Figure 4(b) has adhesive layers 31a and 31b on both sides of the base material 30. Although not shown, a release film or the like may be provided on the side of the adhesive layers 31a and 31b opposite to the base material 30, and a back buffer layer may be provided on the side of the base material 30 opposite to the adhesive layer 31a in the backgrind sheet 2a.

[0181] (Second aspect) A second embodiment of the backgrind sheet of this embodiment is shown in Figure 5. The backgrind sheet 2c shown in Figure 5 has a base material 30, an intermediate layer 32, and an adhesive layer 31 in that order. Although not shown, a release film or the like may be provided on the side of the adhesive layer 31 opposite to the intermediate layer 32, and a back buffer layer may be provided on the side of the base material 30 opposite to the intermediate layer 32.

[0182] (base material) In this embodiment, the substrate used for the backgrind sheet is in the form of a sheet or film, and its constituent material can be, for example, various resins, and the same substrate as that used for the heat-fluidable curable resin film composite sheet described above can be used. The thickness of the substrate used for the backgrind sheet is preferably 5 to 1000 μm, more preferably 10 to 500 μm, even more preferably 15 to 300 μm, and particularly preferably 20 to 150 μm.

[0183] (Middle class) In this embodiment, the intermediate layer used in the backgrind sheet is not particularly limited as long as it is an intermediate layer commonly used in backgrind sheets, and the same type as the intermediate layer used in the aforementioned heat-fluidable curable resin film composite sheet can be used. The thickness of the intermediate layer used in the backgrind sheet is preferably 20 to 300 μm, more preferably 20 to 150 μm, and even more preferably 20 to 100 μm.

[0184] (Adhesive layer) In this embodiment, the adhesive layer used in the backgrind sheet is not particularly limited as long as it can fix and protect the member on which the cured resin film is formed. The constituent materials of the adhesive layer used in the backgrind sheet are not particularly limited, and various adhesives that have been conventionally used in backgrind sheets can be used. Specifically, rubber-based, acrylic-based, silicone-based, and polyvinyl ether-based adhesives can be used. Energy ray curing type, heat foaming type, and water swelling type adhesives may also be used. The thickness of the adhesive layer used in the backgrind sheet is preferably 5 to 50 μm, more preferably 5 to 35 μm, and even more preferably 5 to 25 μm.

[0185] (Method of manufacturing a backgrind sheet) The backgrind sheet of this embodiment can be manufactured by sequentially stacking the above-mentioned layers in corresponding positional relationships. For example, a composite sheet having a laminated structure of a substrate and an adhesive layer can be manufactured in the same manner as the heat-fluidable curable resin film composite sheet described above.

[0186] [Details of the manufacturing method of the semiconductor device according to this embodiment] The details of each step in the semiconductor device manufacturing method of this embodiment will be described below. In the following explanation, we will use the example of a semiconductor wafer having protruding electrodes on its circuit formation surface (α), but as previously stated, the material is not limited to this.

[0187] <Process (S1): Process of forming a curable resin layer on the circuit-forming surface (α) of the component> In step (S1), a heat-fluidable curable resin film (x) is attached to the circuit-forming surface (α) of the component to form a heat-fluidable curable resin layer on the circuit-forming surface (α).

[0188] The following describes in detail the application process (S11) performed in process (S1) and the removal process (S12) which may be performed in process (S1). In the following explanation, we will use the case where composite sheet 1c is used as an example, but of course, composite sheet 1a or 1b may also be used, or the heat-fluidable curable resin film (x) may be directly applied as a single layer. Furthermore, the following explanation will use the case where backgrind sheet 2c is used as an example, but of course, backgrind sheet 2a or 2b can also be used.

[0189] (Process (S11): Pasting process) Figure 6 is a schematic cross-sectional view illustrating the application process. In the bonding process, for example, first, as shown in Figure 6(a), the composite sheet 1c is positioned so that the heat-fluidable curable resin film (x) faces the circuit formation surface (α) of the semiconductor wafer 20. Next, the heat-fluid-curable resin film (x) is brought into contact with the circuit formation surface (α) on the semiconductor wafer 20, and the composite sheet 1c is pressed against the semiconductor wafer 20. By pressing, the heat-fluid-curable resin film (x) is sequentially pressed onto the circuit formation surface (α) of the semiconductor wafer 20. When the composite sheet 1c is pressed onto the semiconductor wafer 20, the heat-fluidable curable resin film (x) deforms due to the pressure through the intermediate layer 11 and enters the recess between the protruding electrodes 21. Finally, as shown in Figure 6(b), the protruding electrodes 21 become embedded by the heat-fluidable curable resin film (x). Furthermore, from the viewpoint of improving the embedding ability of the heat-fluidable curable resin film (x) into uneven surfaces, as described above, it is preferable that the storage modulus (G') of the intermediate layer at 80°C be 0.10 MPa or higher. Also, from the viewpoint of improving bump embedding ability, as described above, it is preferable that the loss tangent (tanδ) of the intermediate layer at 80°C be 1.05 or higher.

[0190] The height of the protruding electrode 21 is not particularly limited, but is preferably 5 to 200 μm, more preferably 10 to 100 μm, and even more preferably 20 to 50 μm. In the present specification, the "height of the protruding electrode" means the distance in the thickness direction of the member between the circuit formation surface and the portion of the protruding electrode 21 that is located at the highest position from the circuit formation surface.

[0191] The width of the protruding electrode 21 is not particularly limited, but is preferably 5 to 200 μm, more preferably 10 to 100 μm, and still more preferably 10 to 50 μm. In the present specification, the "width of the protruding electrode" means the maximum value of the length of a line segment obtained by connecting two different points on the surface of the protruding electrode with a straight line when the protruding electrode is viewed in plan from a direction perpendicular to the circuit formation surface.

[0192] The distance between adjacent protruding electrodes 21 is not particularly limited, but is preferably 20 to 800 μm, more preferably 25 to 500 μm, and still more preferably 30 to 200 μm. In the present specification, the "distance between adjacent protruding electrodes" means the minimum value of the distance between the surfaces of adjacent protruding electrodes.

[0193] As a method for pressing and bonding the composite sheet 1c to the semiconductor wafer 20, a known method of pressing and bonding various sheets to an object can be applied, and examples thereof include a method using a roller-type laminator. The heating temperature when pressing and bonding the composite sheet 1c to the semiconductor wafer 20 is not particularly limited, and may be, for example, 70 to 100°C, and is preferably 75 to 90°C. The pressure when pressing and bonding the composite sheet 1c to the semiconductor wafer 20 is not particularly limited, and may be, for example, 0.1 to 1.5 MPa, and is preferably 0.3 to 1 MPa. The speed when attaching the composite sheet 1c to the semiconductor wafer 20 is not particularly limited, and is usually about 2 to 3 mm / s.

[0194] (Step (S12): Removal step) When the thermally fluid curable resin film (x) is attached using a composite sheet, the removal step (S12) is required. Figure 7 is a schematic cross-sectional view for explaining the state after removal. After the bonding process, as shown in Figure 7, layers other than the thermally fluid curable resin film (x) (support sheet) are removed from the composite sheet 1c to obtain a semiconductor wafer 25 with a thermally fluid curable resin film (x), which comprises a semiconductor wafer 20 and a thermally fluid curable resin film (x) provided on the circuit formation surface (α) of the semiconductor wafer 20. Layers other than the heat-fluidable curable resin film (x) (support sheets) can be removed by known methods.

[0195] (Process (S2): hardening process) After the above steps, in step (S2), the thermofluid-curable resin film (x) is cured to form a cured resin film (x)' on the circuit formation surface (α) of the semiconductor wafer 20. This results in a semiconductor wafer 40 with a cured resin film (x)' on the circuit formation surface (α) of the semiconductor wafer 20. The conditions for curing the heat-fluidable resin film (x) are not particularly limited and can be appropriately adjusted and determined depending on the type of material constituting the heat-fluidable resin film (x). For example, typical thermosetting conditions are a temperature of 90°C to 200°C (preferably 110°C to 170°C, more preferably 120°C to 140°C) for 1 to 5 hours. If pressurization is performed, the pressure is typically 0.2 to 1.0 MPa. For heat curing without pressure, the preferred temperature is 130°C for 4 hours. For pressure-induced heat curing, the preferred conditions are 130°C, 4 hours, and 0.5 MPa. Alternatively, the material may be heated at a temperature T higher than room temperature (preferably 60°C to 100°C, more preferably 70°C to 100°C, and even more preferably 80°C to 100°C) for 15 minutes to 2 hours, and then heated at an even higher temperature than temperature T (preferably 90°C to 200°C, more preferably 110°C to 170°C, and even more preferably 120°C to 140°C) for 1 to 5 hours. If pressurization is performed, the pressure is typically 0.2 to 1.0 MPa. In the case of heat curing without pressure, it is preferable to heat at 90°C for 30 minutes, followed by heating at 130°C for 3 hours. For pressure-induced heat curing, it is preferable to heat at 0.5 MPa, 90°C for 30 minutes, and then at 130°C for 3 hours. Furthermore, as shown in Figure 8(a), even when the cured resin film (x)' does not completely fill the irregularities, meaning that some of the irregularities on the circuit-forming surface (α) of the component (for example, protruding electrodes) are exposed, the presence of the curable resin film at the base of the irregularities reduces the height of the irregularities, thereby suppressing the occurrence of dimples and the deterioration of TTV. In this case, compared to the case where the cured resin film (x)' completely fills the irregularities, less heat-fluidable curable resin film (x) is required, and less heat or energy is needed for curing, thus suppressing the occurrence of dimples and the deterioration of TTV at a low cost. However, as shown in Figure 8(b), if the cured resin film (x)' completely fills in the irregularities, that is, if the irregularities on the circuit-forming surface (α) of the member are not exposed, the irregularities can be made flatter, and the occurrence of dimples and deterioration of TTV can be further suppressed. Therefore, in this embodiment, from the viewpoint of suppressing the occurrence of dimples and deterioration of TTV, it is preferable that the cured resin film (x)' completely fills in the irregularities.

[0196] (Process (S3): Process of attaching the backgrind sheet) After the above steps, in step (S3), the backgrind sheet 2c is attached so that the cured resin film (x)' and the adhesive layer 31 of the backgrind sheet face each other. Figure 9 is a schematic cross-sectional view illustrating the process of attaching the backgrind sheet. A preferred embodiment of the backgrind sheet 2c is as previously described. The method for attaching the backgrind sheet 2c is not particularly limited, similar to process (S11), and known methods for attaching various sheets by pressing them onto an object can be applied, such as using a roller-type laminator. Furthermore, since thinner backgrind sheets generally have higher thickness accuracy, using a thin backgrind sheet tends to improve the TTV of the semiconductor wafer after grinding in this process. In addition, in this process using a cured resin film (X)', the effect of surface irregularities is reduced by filling in the irregularities on the wafer surface, making it possible to grind while suppressing dimple formation even when using a thin backgrind sheet as described above. Specifically, the total thickness of each layer of the backgrind sheet attached to the component is preferably 450 μm or less, more preferably 400 μm or less, even more preferably 350 μm or less, even more preferably 300 μm or less, even more preferably 250 μm or less, even more preferably 200 μm or less, and even more preferably 150 μm or less, from the viewpoint of improving the TTV of the semiconductor wafer after the grinding process. Furthermore, the lower limit of the total thickness is not particularly limited, but is usually 50 μm or more.

[0197] (Process (S4): Back grinding process) After the above process, in step (S4), the side of the component opposite to the circuit formation surface (α) is ground. In other words, the semiconductor wafer 20 is back-ground and thinned. Figure 10 is a schematic cross-sectional view illustrating the back-ground grinding process. Backside grinding of the semiconductor wafer 20 is performed, for example, by fixing the front side of the semiconductor wafer 20 to which a back grind sheet is attached on a fixed table such as a chuck table, and grinding the back side 20b of the semiconductor wafer 20 with a grinder or the like. In this embodiment, the thickness of the semiconductor wafer 20 after grinding can be, for example, 250 μm or less.

[0198] (Process (S5): Heading process) After the above process, if the top of the protruding electrode 21 is covered with a cured resin film (x)', it is preferable to perform a head-exposing process (S5) to expose the top of the protruding electrode 21. Methods for performing the head-exposing process (S5) include one or more treatment methods selected from plasma treatment, laser irradiation, and chemical mechanical polishing (CMP).

[0199] (Step (S6): Formation step of division starting point) In the semiconductor device manufacturing method of this embodiment, a step prior to step (S4) may include a step of forming a dividing starting point for dividing the semiconductor wafer into individual pieces. Methods for forming division starting points for dicing semiconductor wafers into individual pieces include, for example, the pre-dicing method and the stealth dicing (registered trademark) method. Furthermore, when chip fragmentation is performed simultaneously with backside grinding using pre-dicing or stealth dicing, the TTV (thickness variation within the chip) can be kept small, rather than the TTV at the wafer size.

[0200] (Pre-dicing method) The pre-dicing method, as shown in Figure 11 for example, involves forming grooves 61 on the circuit formation surface (α) of the semiconductor wafer 20 along the lines to be divided, and then thinning the semiconductor wafer 20 by grinding the back surface 20b of the semiconductor wafer 20 until at least the grooves 61 are reached, thereby dividing the semiconductor wafer 20 into individual pieces CP. In the pre-dicing method, the starting point for dividing the semiconductor wafer 20 into individual pieces is the groove 61. In one embodiment of the present invention, it is preferable to form the groove 61 after step (B), that is, after forming the cured resin film (x)' on the bump-forming surface 11a of the semiconductor wafer 20. In this case, it is preferable to form the groove 61 from the surface of the cured resin film (x)' toward the interior of the semiconductor wafer 20, as shown in Figure 11. This makes it possible to easily separate the semiconductor wafer 20 on which the cured resin film (x)' has been formed into individual pieces while the cured resin film remains attached. Furthermore, even if a groove 61 is formed inward from the circuit formation surface (α) of the semiconductor wafer 20, and then a cured resin film (x)' is formed on the circuit formation surface (α) of the semiconductor wafer 20, it is still possible to separate the semiconductor wafer 20 with the cured resin film (x)' attached. That is, after thinning the semiconductor wafer 20 by grinding the back surface 20b of the semiconductor wafer 20 until at least the groove 61 is reached, an external force such as pressure is applied, which causes the groove 61 to be used as a dividing point, cleaving the semiconductor wafer 20 and the cured resin film (x)' together, and thus separating the semiconductor wafer 20 with the cured resin film (x)' attached.

[0201] (Stealth dicing method) Stealth dicing is a method of creating a modified region inside a semiconductor wafer using laser light, and then dividing the semiconductor wafer into individual pieces using this modified region as the dividing point. Specifically, as shown in Figure 12, by focusing the laser beam onto the inside of the semiconductor wafer 20 and irradiating it with the laser beam, a modified region 71 is formed as a starting point for division by multiphoton absorption. Then, this modified region 71 forms a cutting starting point region at a predetermined distance inward from the laser beam incident surface along the planned division line of the semiconductor wafer 20. After thinning the semiconductor wafer 20 by grinding the back surface, it is cut using processing pressure such as a grinding wheel to divide it into individual chips and separate them into individual pieces. When forming the modified region 71 before step (S2), the laser light incident surface may be either the circuit formation surface (α) of the semiconductor wafer or the back surface 20b. However, from the viewpoint of minimizing the impact on circuits and other elements formed on the circuit formation surface (α) of the semiconductor wafer, it is preferable that the laser light incident surface be the back surface 20b of the bumped wafer. Furthermore, after step (S2), a cured resin film (x)' is formed on the bump-forming surface 11a of the semiconductor wafer 20. A backgrind sheet 2d or the like may also be attached to the surface of the cured resin film (x)'. Therefore, even when forming the modified region 71 after step (S2), the laser light incident surface is preferably the back surface of the semiconductor wafer. [Examples]

[0202] The present invention is specifically described with reference to the following Examples, but the present invention is not limited to the following Examples. In the event that the measuring instruments and the like used in the Examples are difficult to obtain due to discontinuation of production or the like, measurement may be performed using other instruments having equivalent performance.

[0203] [Production of composite sheet provided with thermosetting resin film (x1)] A composite sheet provided with a thermosetting resin film (x1) was produced by the method shown below.

[0204] <Raw materials for thermosetting resin composition (x1-1)> The raw materials used for producing the thermosetting resin composition (x1-1) are shown below. "Polymer component (A)" (A)-1: Polyvinyl butyral having structural units represented by the following formulas (i)-1, (i)-2 and (i)-3 ("S-LEC BL-10" manufactured by Sekisui Chemical Co., Ltd., weight average molecular weight 25,000, glass transition temperature 59°C).

Chemical Formula

[0205] <Manufacturing Example 1: Preparation of Thermosetting Resin Film (x1)-1 and Composite Sheet (X)-1> (Preparation of thermofluid curable resin film (x)-1) Polymer component (A)-1 (100 parts by mass), epoxy resin (B1)-1 (290 parts by mass), epoxy resin (B1)-2 (220 parts by mass), thermosetting agent (B2)-1 (170 parts by mass), curing accelerator (C)-1 (1 part by mass), and filler (D)-1 (200 parts by mass) were blended, dissolved or dispersed in methyl ethyl ketone, and stirred at 23°C to obtain a thermosetting resin composition in which the total concentration of all components other than the solvent was 45% by mass. Note that all amounts of components other than the solvent shown herein are the amounts of the target product excluding the solvent. Next, using a release film (Lintec Corporation, product name "SP-PET382150", thickness 38 μm), the thermosetting resin composition obtained above was applied to the release surface and dried at 100°C for 2 minutes to produce a thermosetting resin film (x1)-1 with a thickness of 30 μm on the release film. The release surface of another release film (Lintec Corporation, product name "SP-PET381031", thickness 38 μm) was laminated to the exposed surface of the thermosetting resin film (x1)-1. This obtained a laminate in which a thermosetting resin film was sandwiched between release films.

[0206] (Preparation of the intermediate layer) A composition for forming an intermediate layer was obtained by blending 40 parts by mass of aliphatic urethane acrylate (CN966J75 NS, manufactured by Arkema), 40 parts by mass of isobornyl acrylate (IBXA), and 20 parts by mass of dodecyl acrylate, totaling 100 parts by mass, with 3.0 parts by mass of a photopolymerization initiator (Irgacure 1173 (2-hydroxy-2-methyl-1-phenyl-propan-1-one), manufactured by BASF) and 1.5 parts by mass of a chain transfer agent (Kalenz MT PE1 (pentaerythritol tetrakis (3-mercaptobutyrate)), manufactured by Resonaq). The obtained intermediate layer-forming composition was coated onto one side of a polyethylene terephthalate film (Toray Industries, Ltd., "Polyester Film "Lumirror" U34", 75 μm thick) using a knife method to form an intermediate layer-forming composition layer with a thickness of 200 μm. Next, the formed intermediate layer-forming composition layer was laminated with a PET release film (Lintec Corporation, SP-PET381130, 38 μm thick) to isolate the intermediate layer-forming composition layer from oxygen. Subsequently, an illuminance of 80 mW / cm² was applied using a high-pressure mercury lamp. 2 , integrated light intensity 200 mJ / cm 2 After UV irradiation under these conditions, a metal halide lamp was used to achieve an illuminance of 330 mW / cm². 2 , irradiation amount 1260mJ / cm 2 The intermediate layer formation composition layer was cured by ultraviolet irradiation under these conditions, forming an intermediate layer with a thickness of 200 μm. As a result, a laminated sheet (hereinafter also referred to as the "first laminated sheet") was obtained, in which the base material, the intermediate layer, and the release film were laminated in this order in the thickness direction.

[0207] (Preparation of the intermediate delamination layer) At room temperature, an ethylene-vinyl acetate copolymer (weight-average molecular weight 55,000, VA content 20% by mass) was dissolved in toluene to prepare a toluene solution with a solid content concentration of 12% by mass, which was used as the composition for forming the intermediate peel layer. Then, the intermediate release layer formation composition obtained above was applied to the release treatment surface of a newly prepared release film (Lintec Corporation, product name "SP-PET381031", thickness 38 μm), and heated and dried at 100°C for 2 minutes to form an intermediate release layer with a thickness of 10 μm.

[0208] (Creation of composite sheets) In the first laminated sheet obtained as described above, the release film was removed, and the exposed surface of the intermediate release layer obtained as described above was bonded to the exposed surface of the intermediate release layer obtained as described above, thereby obtaining a laminated sheet in which the first laminated sheet and the intermediate release layer were laminated. Next, the release film was removed from the intermediate release layer after lamination, and the release film (the aforementioned "SP-PET381031") of the thermosetting resin film (x1)-1 with double-sided release film obtained above was peeled off and laminated to the exposed surface of the intermediate release layer. As a result, a composite sheet (X)-1 was obtained, consisting of a substrate (thickness 75 μm), an intermediate layer (thickness 200 μm), an intermediate release layer (thickness 10 μm), and a thermosetting resin film (x1)-1 (thickness 30 μm) laminated in this order in the thickness direction.

[0209] <Fabrication of textured wafers> Using a dicer (Disco, product name "DFD6363"), a mirror wafer (8 inches, 250 μm thick) was half-cut at 20 μm intervals with a depth of 35 μm and grooves of 20 μm, to create a textured wafer with pseudo-bumps (height: 35 μm, width: 20 μm, pitch: 40 μm). The uneven wafer was used in the following evaluation as a substitute for a component having irregularities on the circuit formation surface (α).

[0210] [Example 1 and Comparative Examples 1-3] In Example 1 and Comparative Examples 1-3, the backgrinding process was carried out using the composite sheets and backgrind sheets shown in Table 1, and the measurements and evaluations described later were performed. The following materials were used as the backgrind sheet. ·Back grind sheet 1: "Adwill E-3100V" manufactured by Lintec Corporation, the total thickness of the base material layer and the intermediate layer is 80 μm, and the thickness of the pressure-sensitive adhesive layer is 20 μm. ·Back grind sheet 2: "Adwill E-9486" manufactured by Lintec Corporation, the total thickness of the base material layer and the intermediate layer is 475 μm, and the thickness of the pressure-sensitive adhesive layer is 10 μm.

[0211] (Example 1) Using a roller-type laminator (manufactured by Lintec Corporation, product name "RAD-3520 F / 12") as the bonding apparatus, under the following bonding conditions, the surface of the thermosetting resin film (x1)-1 of the composite sheet (X)-1 was bonded to the surface having the pseudo-bumps of the mirror wafer on which pseudo-bumps were formed, and the support sheet (a laminate of a base material, an intermediate layer, and an intermediate release layer) was peeled off. (Bonding conditions) ·Table temperature: 80°C ·Bonding speed: 2 mm / s ·Bonding pressure: 0.5 MPa ·Roller bonding height: 0 μm Next, after heating at 90°C for 30 minutes, the assembly was heated at 130°C for 3 hours to thermally cure the thermosetting resin film (x1)-1, thereby forming a cured resin film. Thereafter, using a roller-type laminator (manufactured by Lintec Corporation, product name "RAD-3520 F / 12") as the bonding apparatus, back grind sheet 1 was bonded to the surface on which the cured resin film was formed under the aforementioned bonding conditions. Then, using a grinding apparatus (manufactured by Disco Corporation, grinder DGP8760), back grinding was performed until the thickness reached 100 μm excluding the pseudo-bump portions, and back grind sheet 1 was peeled off to obtain Wafer E1. Note that when peeling back grind sheet 1, energy ray irradiation was performed under the following conditions. ·UV irradiation apparatus: manufactured by Lintec Corporation, product name "RAD-2010m / 12" ·Conditions: Illuminance: 230 mW / cm 2 , Light quantity: 380 mJ / cm 2 (Dominant wavelength: 365 nm)

[0212] (Comparative Example 1) Using the same attachment apparatus and conditions as in Example 1, the surface of the thermosetting resin film (x1)-1 of the composite sheet (X)-1 was attached to the surface of the mirror wafer having pseudo-bumps. Next, using a grinding machine (DISCO, DGP8760 grinder), backgrinding was performed until the thickness reached 100 μm, excluding the pseudo-bump areas, and the support sheet of composite sheet (X)-1 was peeled off. Subsequently, the thermosetting resin film (x1)-1 was heated at 90°C for 30 minutes, and then heated at 130°C for 3 hours to thermoset it and obtain wafer C1.

[0213] (Comparative Example 2) A roller-type laminator (Lintec Corporation, product name "RAD-3520 F / 12") was used as the lamination device, and the backgrind sheet 1 was attached to the surface of a mirror wafer with pseudo-bumps, under the following lamination conditions. (Attachment conditions) • Table temperature: 80℃ • Application speed: 2mm / s • Adhesion pressure: 0.5 MPa • Roller application height: 0 μm Then, using a grinding device (DISCO Corporation, Grinder DGP8760), the back surface was ground until the thickness reached 100 μm, excluding the pseudo-bump areas, and the back-grind sheet 1 was peeled off to obtain wafer C2. Furthermore, when removing the backgrind sheet 1, energy beam irradiation was performed under the following conditions. • UV irradiation device: Manufactured by Lintec Corporation, product name "RAD-2010m / 12" ·Condition: Illuminance: 230mW / cm 2 , Light amount: 380mJ / cm 2 (Dominant wavelength: 365nm)

[0214] (Comparative Example 3) Wafer C3 was obtained in the same manner as in Comparative Example 2, except that backgrind sheet 2 was used as the backgrind sheet. Furthermore, when removing the backgrind sheet 2, energy beam irradiation was performed under the following conditions. • UV irradiation device: Manufactured by Lintec Corporation, product name "RAD-2010m / 12" ·Condition: Illuminance: 230mW / cm 2 , Light intensity: 1120mJ / cm 2 (Dominant wavelength: 365nm)

[0215] [evaluation] TTV, dimples, air bubbles, and adhesive residue were evaluated using the method described below.

[0216] <Thickness uniformity (TTV) of the workpiece after backside grinding> For wafers E1 and C1-C3, the thickness of the entire wafer surface after backside grinding was measured using a thickness measuring device (Hamamatsu Photonics, product name "C11011-01W") at a measurement pitch of 10 mm. From the obtained thicknesses at each point, the average thickness and standard deviation of the thickness were calculated. A group of data points with thicknesses between [average - (standard deviation × 3)] and [average + (standard deviation × 3)] was extracted, and the difference between the maximum and minimum thicknesses within this data group was calculated as TTV. Then, we evaluated TTV according to the following criteria. Rating A: TTV is 4.5 μm or less Rating B: TTV is greater than 4.5μm

[0217] <Presence or absence of dimples> For wafers E1 and C1-C3, the back surface of the wafers was visually inspected to confirm the presence or absence of dimples. Then, the presence or absence of dimples was evaluated according to the following criteria. Rating A: No dimples have formed. Rating C: Dimples are clearly present.

[0218] <Presence or absence of air bubbles> During the fabrication of wafers E1 and C1-C3, the presence or absence of bubbles around the pseudo-bumps was observed on the pseudo-bump wafers immediately before grinding using a digital microscope (Keyence Corporation, model name "VHX-7000") at a magnification of 300x. The observation conditions when checking for the presence or absence of bubbles in Example 1 and Comparative Examples 1-3 are as follows. • Example 1: Observation with the backgrind sheet 1 attached to the cured resin film. • Comparative Example 1: Observation with the composite sheet (before curing) attached. • Comparative Example 2: Observed with Backgrind Sheet 1 attached. • Comparative Example 3: Observed with Backgrind Sheet 2 attached. Then, the presence or absence of air bubbles was evaluated according to the following criteria. Rating A: No air bubbles present. Rating B: Bubbles are present.

[0219] <Presence or absence of adhesive residue> For wafers E1 and C1, the cured resin film surface was observed, and for wafers C2 and C3, the pseudo-bump formation surface was observed, using a digital microscope (Keyence Corporation, model name "VHX-7000") at a magnification of 300x. Then, the presence or absence of adhesive residue was evaluated according to the following criteria. Evaluation A: No adhesive residue is left behind, and the support sheet or backgrind sheet is easy to peel off. Evaluation B: No adhesive residue was generated, but the peeling force of the support sheet or backgrind sheet was high. Rating C: Adhesive residue is present.

[0220] In each evaluation, a rating of A was considered a pass, while a rating of B or C was considered a fail.

[0221] The results are shown in Table 1.

[0222] [Table 1]

[0223] Table 1 shows that in Example 1, where a cured resin film was formed on the pseudo-bump surface and then a backgrind sheet was applied, the occurrence of dimples was suppressed, the TTV after the backgrinding process was maintained well, and there were no air bubbles and adhesive residue was suppressed. On the other hand, in Comparative Example 1, where only a heat-fluidable curable resin film composite sheet was attached to the pseudo-bump-forming surface, the TTV deteriorated significantly. In Comparative Examples 2 and 3, where only a backgrind sheet was attached to the pseudo-bump-forming surface, not only did the TTV deteriorate, but at least one of the following occurred: dimples, air bubbles, or adhesive residue. [Explanation of Symbols]

[0224] (α) Circuit formation surface (x) Thermally fluid curable resin film (x)' Cured resin film 1a, 1b, 1c Composite Sheet 2a, 2b, 2c Backgrind Sheet 10 Base material 11 Middle Class 13 Intermediate delamination layer 20 Semiconductor wafers 20b Back surface of semiconductor wafer 20 21 Protruding electrode 25 Semiconductor wafer with thermally fluid curable resin film (x) 30 Base material 31, 31a, 31b Adhesive layer 32 Middle Class 40 Semiconductor wafers with cured resin film 61 Groove 71 Modification Area

Claims

1. A method for manufacturing a semiconductor device using a member having a circuit forming surface (α) and having irregularities on the circuit forming surface (α), Step (S1) involves attaching a heat-fluidable curable resin film (x) to the circuit-forming surface (α) to form a heat-fluidable curable resin layer, The process of curing the aforementioned heat-fluidable curable resin layer to form a cured resin film (S2), Step (S3) involves attaching a backgrind sheet to the side of the cured resin film opposite to the circuit-forming surface (α), A method for manufacturing a semiconductor device, comprising the step (S4) of grinding the surface of the member opposite to the circuit forming surface (α).

2. The method for manufacturing a semiconductor device according to claim 1, wherein the complex viscosity of the heat-fluidable curable resin film at 80°C is 15,000 Pa·s or less.

3. Furthermore, the method for manufacturing a semiconductor device according to claim 2, wherein the complex viscosity of the heat-fluidable curable resin film (x) at 130°C is 50 Pa·s or more.

4. A method for manufacturing a semiconductor device according to any one of claims 1 to 3, wherein the heat-fluid curable resin film is further thermosetting.

5. A method for manufacturing a semiconductor device according to any one of claims 1 to 3, wherein the thermal fluid curable resin film is further energy ray curable.

6. A method for manufacturing a semiconductor device according to any one of claims 1 to 3, wherein the heat-fluidable curable resin film (x) is further a heat-fluidable curable resin film composite sheet having a support sheet.

7. The method for manufacturing a semiconductor device according to any one of claims 1 to 3, wherein the member is a member having a protruding electrode on the circuit forming surface (α).

8. The method for manufacturing a semiconductor device according to claim 7, wherein the height of the protruding electrode is 200 μm or less.

9. A method for manufacturing a semiconductor device according to claim 7, further comprising the step (S5) of exposing the top portion of the protruding electrode after the above step (S4).

10. A thermofluid-curable resin film used in a method for manufacturing a semiconductor device according to any one of claims 1 to 3.

11. A thermosetting, thermofluid curable resin film according to claim 10.

12. A heat-fluid curable resin film according to claim 10, which is energy-ray curable.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive sheet

    JP2000328023A